CORAK ANEKDOT INDONESIA - doyin, mukh (LITERA, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAa8AAAFmCAIAAABV7oIqAAAgAElEQVR4nOy9d1xUR9v/f1Ke+/G+o4mJiUZFY0ENKoioSBUDIh1FQAEp0rEgoDRpUkREioqCdBGUIiACSpfeewdp0uvCLgu7y9b5/TG/e788aIwmFmLm/Qcv9uw50/acz7nmmplrMIBAIP4UNBqNRqN96lIg3hvYpy4AAvF3BYfD4fH4T10KxHsDqSECgUAAgNQQgUAgIEgNEQgEAgCkhosB1n+Z//HVcxb8s+Dy1x55NeX5B3/vwjdc8pb5LijDa4v09gm+TS4IxF8HqeFihMlksv9vbm6enZ19+2vnqwOLxZqf1JtPXpDvH56MQHxmIDX89GRkZGhoaBgaGtrZ2SkqKt66dQseT0hIOHr0qJaWlrq6upqaWmVlJQCgsbHxzJkzR44cOXr06LFjx5SUlDQ1Nevq6uYnmJKSYmpqypa2qakpS0vLo0eP6urqwkRCQ0MVFRXv37//amHi4uIuXrxIJBLhx+Hh4XPnzqmpqTU1NbETP3r0qKam5osXL5ycnNglOXr06K1btwoLC48cOXLkyJFz586Nj48DAOzs7NTU1J4/f+7g4HDkyBErKytTU9Njx46dO3fu3r17ZDJ5fjsYGhrCStnZ2Q0ODgIAYmJiDAwMvL29PT09r1+/7uHhoaenFx8fDy/Jz8/X09Pz8vLy9vaurKzMyclxcXGJiIhg1/3evXtOTk5Pnz5NSEi4cuXK9evXYVJubm5JSUkMBgP8V+V7enp8fX09PDyuXLkSGBhIIBAAAP39/bdu3fL09GxoaIAJtra2enp6XrlyJS8vLzg4+OrVq9euXfP09Lx8+XJSUhJMLSEh4erVq+7u7rCC2dnZV65ccXd3Dw4OxuFwMJ3JycmYmJjh4eE/fdsg3jtIDT8xDx48WLlypaWlZV1dXWtr640bNwQFBel0upeX148//ujt7f3y5cuamhp+fv7NmzfX1dURicTjx49jGHbp0qXKysqHDx9iGGZgYMA23BgMhrCwMIZhmZmZAAAWi0Wj0aKiojAM09XVJZPJOTk5XFxc/v7+/f39CwrDYrFERES++OKL3NxceIRCoXh6emIYJiAgMDY2BgAYHBzU1tY2MzObnZ0NCwvDMExERKSysjIlJUVVVRWHwwkJCWEYFhISwmKx3N3d9+/fn5WVNTEx8eDBAwzDxMTEGhsbKysrra2tV6xYoa+vPzc3x2QyfX19165de+PGjcrKyoyMjL179+7Zs2diYsLR0VFVVTUiIoKDg0NQUDAhIUFfX9/T0xMWD4fDOTs7f/HFF1ZWVng8vqOjg5ub+4svvvD29oYnxMXFiYqKjo6OpqSkfPnll3v27Ons7CwqKnJ0dFy9erWWlhbU/YKCAm5u7vPnz5eXlwcGBm7dulVCQmJiYoJMJtvY2GAYJigoCPWRSCReuHBBRUVlYmLi9u3bGIYpKirGx8e7urra29uzWKyLFy/KyMjk5eU9ePBg8+bNAwMD4+Pjhw8fxjCspKSESqXCgmVkZHz99dePHj36oHcX4p1Aavgp6e7u3rJli7S0NHsSL4PBePLkSUVFxU8//aSurs4+s7GxEcOwU6dOsViskJCQVatWlZaWAgAIBAKGYfr6+tDMAQAUFBQICgpiGGZsbAz+a/hUV1d///33Pj4+g4ODOjo6sbGx8OQFnd/a2louLi4Mw+zt7dkHExISBAQEMAzT0NCA2hEYGBgQEMDO3dTUFACAw+FKSkoAAC4uLkuXLq2qqnr+/LmKigrbqiIQCEuWLDl69Cg7azMzMwzD8vLyBgYGlixZoqOjQ6fT4bfFxcX/+te/9PT0mpqauru75+bmeHh4pKWlKRTK1NTUwMAAu3ixsbEYhoWGhsIyKCoqfvfdd998882zZ88AAO3t7XJycgCArq6uJUuW/Pbbb+wL7e3tMQx7/PgxhULh4uKSkpJiW8Tw5XHmzBkAQHBw8Lp162AjQy2Lioo6f/48AKC+vh7DMFdXVwDA+Ph4bW3t4ODg1q1bfXx8YDpubm4jIyMAAG1tbQzD2B4PKpVqbGz873//W01NDc3fXjwgNfyUZGRkYBjm6+u74HhcXByGYe7u7uwjMzMzX3/9NR8f3/T0dHx8PDc3d1ZWVkFBgZ2dnaqq6osXL8B/pe3SpUuRkZFycnJr165tbm6Gl5eVlf30008nTpwQFha2s7P7vfJcunTJ19dXUlJy06ZN3d3d8GBERERmZqa5uTmGYdAou3v3LuzOT01N/etf/xIVFb1///6pU6cKCgoAAL6+vitWrDAyMpKQkKipqWEnTqfTv/nmG0VFRfaRzMzMJUuWeHh4QEWLiIhgf8VkMjk4OLi4uObm5gAABAKBl5dXRkaGRCItKDNULmgMDg0NWVlZBQcHb9iwYePGjS0tLd3d3Xp6evDM1atXi4mJsS8sLi7+z3/+4+jomJ+fj2HYlStX2F/h8fhffvll69atsLJeXl6qqqoYhl29ehUAEBMTA18AL1++xDDMxMSkpaUFyvHLly/Xr1+/detWDw+Pp0+fspUOqiG0LgEAVVVVRkZGNjY2//rXv6DvAvlkFwNIDT8lT58+xTDs9u3b7CPwqYCdyvlqiMfjv/76a35+fiKRmJCQwMfHFxAQcP78+WXLlgUGBrJPe/nypba2dmlpqa+vL4ZhN27cgMfLyspWrVrFy8uLYdiRI0fgY7lgQLa7u1tRUbG6utrHxwfDsOjoaHg8LCwsPT19ZmZGUVFx2bJlkZGRQUFBsMw4HO7rr7+WlJSMjIwUExOD5tjNmzeXLVu2fv36//znP/PLRqVSF6gh7C16eHjAzvi9e/fmN86GDRu2bdsG5Q+Px0M1fHVACaoh9NkNDg6ampoODg5mZmZiGCYsLJyVlWVmZgYAYDKZK1eunK+G1dXV//nPf+zt7YODgzEMgwYdu0G4ubm3bdsGALh9+3ZYWNjw8PDBgwf/53/+JycnJzExEdqG3d3dGIYdP37cy8tLUlIStmdYWNjmzZsxDPv++++FhYUbGxvBK2ro5eUVEBCQk5Pz73//28rK6o33COLjgdTwU1JVVbVkyRJlZeUFpkFeXt6XX3554cIF9hHYJ1VSUmIymcHBwVxcXPX19TgcTlRUdPv27bDnyGKx4uPjt2zZIiUldeDAgWXLlomJiUG3fVlZ2YoVKxwcHLy8vDAM09HRmT+AAP/ev39/69at0tLSBw4c+Pe//y0rKwt7jvfu3cvIyAAA1NfXr1279vvvv1dSUoIyNzU1BY0jAEB1dXVfXx+TyfT29v7xxx9DQ0NlZGS++uqrhIQEWAUGg7F06dL5anjlyhUMw6qrq58/f45h2J07d9iFIRKJq1atYndsCQTC7t27X6uGkZGRGIYVFxcDAAYGBs6dOwct5evXr2MYpqqqamNjA7/69ttvYYIwi+joaCijLS0tbLsPfjU7O7tx48Y9e/YAAPz8/Pz9/WEF16xZw8HBYWxsbGlpCQDo7u7+6quvbt26NTU1lZiYCACYm5ubmZkZHx9va2uzs7P74osvnJ2dAQA6OjpsNaTT6dLS0srKymfOnFm+fPnq1avheBHik4PU8FNCJBL19PTmd5bxeHx5efnU1JSKisry5ctbW1vhcW9v76VLl8JHzsTEZNmyZeXl5QCAvLw8DMPU1dVJJBKJRNLS0srKyqJSqXQ6HRpcUIwqKiq+/vprLy+vubk5TU1NDMNcXFzYrkaY79GjR9PS0qhUKplMNjAwwDAM2np37ty5cuUKHKVNS0tbsmQJhmF3794FAExOTkJthYlERERMTU1ZWFh88cUXTU1NbW1t69ev/+GHH7Kzs2EWX331lYqKCjy5sLDw559/1tLSotFoQ0NDP/300/bt26empuC3kZGR3377Ldu/SaFQtm/frqio+OocoMTERLYlOzExYWlp2dPTAwCYnZ2Ftbh8+TIAoLe3d+nSpZKSkvCqvr4+Hh4ePj4+HA5HIpF4eXl5eHgmJibgt1FRUUuWLAkPDwcABAUFhYSEwOOZmZn/+7//i2EY1DjozL1+/Tr8tqCgIDMz08PDA37s6OhYtWqVl5cXAEBfXx/DMNjrT01NPXv2bG5ubmVlpZub27/+9S/2LALEpwWp4SdmeHhYV1d369atSkpKhoaGRkZGUGh6e3sVFRWlpKQMDQ21tbVFRUWhZ6qlpUVNTW3Tpk12dnbPnz+fnp6+cOHCpk2boqOjIyMjhYWFoWKSSCRbW9stW7acOnWqtrbWw8ODk5NTT0+vr6+PQCCcOHFi3bp1d+7cgepDp9ODgoJ27Njh4eHBZDJHR0d1dHQ2b96so6OTl5fHz8+/YcOGyclJWODQ0NBly5ZB+Q4ODl61atXRo0evXLly6tSp/fv3p6WliYmJrVq1Sk9Pj0AgVFZWrl+/fvny5ZmZmVlZWdAUMjQ0NDY2VldXd3BwYAtQenr6rl27pKSkfH19nZ2deXl5XV1d2X63u3fvYhj2008/xcXFzW+9uro6SUlJOFTd3d2dkJDAycnp4uICR2OIRCI3N7eCggIAICEhAcOwtWvXurq6mpiYqKqqamtr19bWwnQKCgo2btwoLy8fHBzs7e3Ny8t78eJFMpk8NjamoKCgqKjY1tYGz7x16xbbieHh4YFhGDc3t6Ghoaqqqri4eHJyMj8/v7W1dUREhIaGhrKy8uDgYGlpKTc3N4ZhT5486ezs5Obm1tbWhqmFh4djGLZq1aqUlBT2CBLiU4HU8FMC+2VUKrW5uTkxMfHRo0fFxcUUCgUex+PxBQUFcXFxSUlJXV1d8JKRkZGmpqb29vbW1taOjg4qlUoikeBwQUtLS0NDQ2dnJwBgbm6upqamo6Ojqampv7+/sbGxvb29oaEBdpwJBEJDQ0N9fT30yjEYjI6Ojrq6upqaGgaDgcfja2trX7x4UVdX19HRkZ+fn5aWNjs7y/Yz1tTU9Pf3s1is5ubmhoaGlpaW7OzspKSkqqqq3t7eqqqqhoaG3Nxc2NFub29PT09vb28fHR2tra3NyMh49OhRcnJyS0sLrBHb3BsYGEhISAgPD09MTCwrK5vfSjU1NTk5ORkZGexpj+xL0tPTc3Nzc3NzcTjcixcv0tLSysrK2GZva2trRUUFi8UaHBzMz89//vx5ZmZmQkJCUVERHCBmMpmwUl1dXXfv3vXw8Lh58+bz589hqaanp/Pz8/Py8uDsIliYmJgYOPTR1taWm5v79OnTuLi4xMTEiooKPB6flpbm5uZ27dq1iIgIeFVVVVVCQkJeXl5NTU17e/vDhw/v3bsH7cSEhAR3d/f09PSWlhYGg4HGUj4tSA0RiP/HfO/BX+EPDb35HlvEIgGpIQKBQACA1BCBQCAgSA0RCAQCAKSGCAQCAUFqiEAgEAAgNUS8DZ88qCqFQkHBrxAfGqSGiD+GxWLR6XQ4Re6T5E6j0d4p5C0C8SdAaoh4K0gk0tDQ0CfJGk3KQ3wckBoiEAgEAEgNEQgEAoLUEIFAIABAaohAIBAQpIYIBAIBAFJDBOLPwWQyBwYG3lfMm08Cg8F48w7a/zSQGiIQfwYWi0Uikf7WajI4OMjeJhABkBoiEH8FdrDYvyPINlwAUkMEAoEAAKkhArH4+fuan38vkBq+CXQXIj45dDp9fHwc3YofAaSGr4dIJE5PT6NbEPLmiAmvHVclEoljY2PzL6RSqQMDA729ve+/fJ81dDqdQCCgW/Ej8A9Vw4mJiTePpk1PT8O9wN+STx7z6oOSkZFhamoaHBwM5tnLRCLxypUrtra29fX1r16SmpoqLi5+79499vkdHR2ysrJWVlavnjw+Pu7l5XX+/HlfX9/w8HAnJydra+uOjo63L2FcXNzNmzffuWKLns/4pnqPsP7LX0znn6iGLBZrZmbmbeJTvWX7Tk1NjY6O/uVyLV6Gh4d37Njx008/zbfsgoODMQxTUFDA4/GvXtLd3c3FxeXn58c+QiAQJCQkHBwcXj15dnbWy8tr48aNsbGx1dXVOTk5zs7OoqKiRUVFb1nCgIAAGxubd6wW4jNhZmZmYGDgr6fzD1XDtzztLc9kMBjsfdA/S1gslrm5+bZt265fv87eA9rJyemXX35xdHSkUqldXV2tra0MBmN0dLS+vn50dJRKpUpJSd2/fx8A0NfXV1hYSCQSDQ0NfXx8WltbCwoK2PvKQ/Lz86WkpAYHB9lHtLS0lJSUWCwWk8msqqoqKCiAmymPj4/X19e3tLSQSCS473N/f/+LFy/6+vooFEpvb+/AwMDExERBQUF3dzdYZObV3Nwc3McZ8R5hMBjvpVX/iWqIeFeIROKdO3fu3LmzceNGGOUwMjIyMDBQWFjYzMxsbGxMW1t7x44dFAolPT2dg4Pj4cOHNBrt0KFDjx496uvrU1ZWtrW1HRkZ0dPTO3r0qKurq4CAgKam5nxnRWZmpoSERFdXF/tIeHj49u3bR0ZGAgICTp06ZWNjIy4unpaWlpOTs2bNmosXL05MTJw/f/7IkSPJyckaGhpaWlo4HM7Y2JiPj8/CwkJcXFxYWLi1tfUTtNfv09vbO1/xEYsKpIafD+/Le/IqRCLR29t7ZGRk//79np6eRCLx7Nmzubm5hw4dMjY2BgC4u7tLSEgwmczBwUFubu6ysjIAgIyMzJkzZ+zt7bOysmA6CgoKEhIS09PTLS0t27Ztq6ysZGfxWjXk4+N7+vSpvLz8ixcvAAA3btzYtWtXf3+/uro67HEHBwffvHmTRqNdv35dXFycyWS6u7svWbIkOTl5dHRUUlJyfld9MQBN109dCsTrQWr4WTE3Nwd7qe83WSKRePXqVQDAjRs3fv3119DQUA8PDzqdzs/PD9UwMTHx9OnTAICpqan9+/fX1dUBAI4ePbpx40ZRUVEcDgcAYDAY6urqHh4eMME9e/bMdwsmJiYKCgr29PSwj+jp6eno6CQkJEhJSY2PjwMA2tvbt2/f3tfXl52dLSYm1tzcbGVlNT09DQDIzMw8f/48ACAoKGjNmjVkMhkAoKWl5ePj836b4i+CesqLmX+oGrJYLCKRSKfTP3VB3ifQxUan09+7eUilUl1cXAAAk5OTW7ZsWblyZXt7OwBgz549UAT9/PwOHTo0OztbVla2bt26xsZGAMDhw4f9/f2vXbsmLS3d3NxMp9M1NTU9PT0BAGNjYzw8PNXV1eC/fr3k5GQ+Pr6RkRGYXVpampiYWGVlZUVFxcaNG2trawEAGRkZsrKyOBxuenr6t99+O3HixMOHD2EJw8PDxcTEAABBQUGrVq0ikUgAAHV19cDAwPfbFIj3xVuOZH5M/qFqCAAYHR2lUCifuhR/D4qKiuTl5RMSEmg0mq+vr6GhIYPByMvL4+Pjk5eXr62traqq4ubmVlNTO3369LZt23x9fevq6kRERExNTfF4vJ2dnaioaG5u7okTJ06cONHX1zczMyMkJOTn54fH46GIR0VF8fLy3rp1KyYmxsPDw9DQkG052tjYqKiohIaG6unpxcbGwoNBQUGbN2+GtuTY2NihQ4c4ODhKSkqcnZ2XLVsWHR0NADhx4oSsrOw7zZRCfDTGxsZmZmY+dSn+D/9QNXz58iXsviHehsbGxoyMjOLi4rm5OQqFAjvjpaWleXl5mZmZzc3NAIDq6ur79+83NTW1trbm5ua2tLTk5eVlZ2fDmcP5+fmtra3l5eU5OTlwGKG8vDw/Px/2cxkMRmtra15e3rNnz5KTkzMzM+dLGJFITExMjImJge5ISGpqqr+/P7TuJyYmkpOTk5OTq6urq6urk5KScnJyWCxWZWVlREQECtOCeEv+iWoIu8lkMvlvHYDkHwuVSh0eHnZwcCgsLPzUZUF8VvxD1RD+g9Tw70hmZqawsLCHh8ffOtIqYhHyT1RDxN+a1tbWx48fI2/gewdZBkgNEX8n5j+x6Ol9jwwNDb05Nsc/AaSGCAQCUCgU5HlAarhYmJqampiYIBAIQ0NDg4ODcDbW5OQkgUB4+fJlR0fH/PlA7e3tBQUFRUVF81f7zs7Ojo2NEYnE0dFRBoPBYrEmJiYmJycnJiZ+b8bv+1pe/ScCyrNYLDwev2Bkn0Ag4HC4qampDzRFeXZ2dnh4+EOkjPgMQGr46YE9vp6ennPnzp08eTIsLCwiIuLixYtZWVkeHh7a2to3b960t7fX1dWFc579/f2trKzMzc3PnTtnZGQEDwIA+vr63N3dlZWV79y5Q6FQmExmaWkpvHxqaurVfKOjo62srP7inC8ikWhnZ/fs2bM/UeuysjIdHZ27d++yD5aVlRkZGTk6OsKZN38aFosVFxf38OHD+TL94MEDW1tbZ2dnQ0PDioqKv5I+gg2TyRwZGfk87Eqkhp8euLiYyWS6urry8fG1tLSMj48HBgZWVFTY29tv3ry5vb19YGBgw4YN1tbW5eXlYmJi7e3tRCJxcnLSwMAgNzcXpkOj0QICAr788svs7GyosCQSSVBQMDMz87X5ZmZmhoWF/cX1AHNzc7dv3y4pKQEAJCYm2tjYvI29CatMIBCOHDnyxRdfpKSkwOM4HO7ixYs+Pj5/3ScYEhJy48YN9sf09HRJScn8/PyWlhYLC4vQ0FDkdvwTwBt1wRE8Hv957DaF1HARkZiYqKysDJ/SyclJFot17dq13bt3w5DRqqqqGRkZISEhfHx8MJAMAIDJZMJOMfyYlJS0YsWKtrY2dprHjh1raWlpb29vbGzs7u5+9uzZ06dP6XT6zMxMTU3N4OAgk8nMzc0tLy/v6+uj0WhtbW0dHR1MJrOvr+/evXsZGRlMJrO3t7exsbGzs7O6uppEIk1OTj569Cg2Nra3txeHwzU1NU1PTzMYDGNj482bN1dUVNBotMHBwdTU1KKiIiiOBAIhLS3t0aNHCyK4hIaGKioq8vLywmAzNBotPj4ersObm5srLS3NzMyEhi2LxXrx4kVzc3NnZ+fLly/hmHJDQ0NCQgJcCDg6Otre3j40NPTixYuxsbHu7m5YI9g4bm5ucnJy7EaDoRPIZHJbW1tjYyOJRKJSqYODg0NDQ83NzTU1NQCAoaGhqqoqtlkN1x02NDRQqVQ6nT4wMDA0NDQ+Pt7T00Oj0QgEQllZWWNjI4wu1dvbOz09PTg4WFFRwU6BQqE0NTU1NTXh8fjZ2dnFti7tbZiZmfmMY/AgNVxEBAQE8PDwxMfHW1hYuLm5AQC8vLzWr18fEBCgrq4uLy8/NTXV2NgoIiIiLCx86tQpHR2dpKQkKpXKVsP4+PgffvgBxgGEKCsrV1dXu7u7r1ix4ujRo5aWljt27Lh7925vby8XF5eIiAiBQLh27drSpUujo6Ph+l8jI6P4+HhjY2N3d3dNTc3bt2/fv3//559/5uHh2bFjR1JSkoWFhY+Pj6mpqZWVVVZWFgcHR1hYGIVCERMT4+LicnV1bWlpOXPmzJkzZ0REREJCQvB4/KVLl+zs7E6fPn3u3Ln5VQ4MDKysrDx16pSgoCAOh2OxWDExMfX19VQq1dfX9+rVq+bm5rq6ulNTU6mpqRoaGu7u7vv27Tt06FB+fv7Tp08tLCwcHR2lpKSSk5MzMjL4+Pj4+fllZGTCw8P19fVlZGTYUXjT0tJWrVqloqISEBCQn58PAJicnPTx8fH29jYzM7O2ti4oKDh27Nj+/futrKx27txpZWVla2t74MABBQUFHA6Hx+OvXbumoaEhJibm7e1NJpPd3d1379597NgxBQWFqqqqy5cvq6qq7tmz5969e+Pj4yoqKjIyMk5OTuLi4vr6+lNTU7Ozs66urpcvX9bU1FRRUYmIiBgbG/tIN9Z7AhqGn4cZ+Fo+oBp+3sHxPwSWlpYrVqwIDQ3V0NAwNTWlUqnXr1/fvn17SUlJVVWViIgIDNPS3d0dGBhoZmamrq6+fv36sLAwdgqPHj364Ycf4FI5iIKCQldXF4vFEhYWDgkJAQB4eXnJysoCAAICAhQVFalU6tzcHJQtAIC+vn5DQ4Oqqqq+vv7g4KCzs7OQkBCRSFRTU/Py8mppaSksLNy4cWNMTExra2t3dzeNRjty5AgMnKWtrX369GkGg0EgECoqKqqrq+Xl5U+dOtXc3MzLy3v9+vWOjo6WlhYwb3LMtWvXWlpaJicneXh4jh8/Pjs7+/jx47a2tpSUFD4+vubm5vz8/PXr14eHh6uqqsbHxwMAjh07du7cuZ6eHkFBwaioqKGhIQUFBTExMTKZrKKicuLEiaqqqrGxMWdn599++w2Gb4A8efLEwsLi4MGD27Ztu3PnTkBAwP79+xsaGnJycjZv3pyYmGhqanro0CEqlern57dq1aq6urqOjo61a9cWFxdPTk7m5+fPzMxYWlrC8BDNzc1r1661t7fPy8vr7e0tLi6m0Whnz549fPgwjUZzdXX95ZdfOjs7e3t7N2zYEBsbm5OTIyAgAAAoLS1dvXp1QUHB5+Fr+5z4sGrIYDA+szgxHxQbGxteXl74f0dHB51O9/Dw2Lt3LxxSuHz5Mjc39wKDwtbW1sLCgv3x0aNH33333fwdReTl5eF4tLCwcE5ODgDAx8fn2LFjAICAgAATExMAAOySKygoPHny5MaNG0NDQ9zc3MbGxhkZGTExMQ0NDQQCQVxcHIacgVabiIjIvn37XFxcSCTS0aNH79y5AwC4cOGCqakpAKCtre3s2bNhYWFGRkbGxsYkEikgIEBYWJifn9/b23u+Cnh6esJuaUNDw9atWy9duvTo0aOuri5vb+9t27bFxsbGxMTcunWrtbX1/Pnz2traWVlZWlpaXV1dXV1dUNRSU1Nv3rwZHR1NIBAOHz4MSwIAuHr1qrq6Olt22ZnOzMz4+vpu375dV1eXj4/P3t7eycnp7t27g4ODLi4usDGDg4OVlJQAAAQCYf/+/UVFRSwWKyIiwt3dXUtLS0ZGBgBQVVXFxcVVXFwMAJienr53756Xl5exsbG8vDwAICQkBKYwOjq6evVqf3//xsZGYWHhtra2+AIy4DIAACAASURBVPh4TU1N9FwsQj5sT5lAIHzeG4a8F9hGtKGh4bp16/r6+thfOTg4bNmyBYa5V1ZWNjU1DQkJycvLo1AoExMT7e3tJ06cuHfvHvv8ysrK77777s6dO3g8nkgkZmdnnzp1amJiAo/H79ix48mTJwAADw+P3377DQBw+/ZtQUFBGNSgubmZh4dHQEBgaGiISqXKyckdOXJkYGBgcnISbpi1Y8cOOFxTXV2dkpJCoVCCg4O5uLjGxsYUFRVv374NADAxMdHS0iKTyadPn+bl5R0eHjYxMdHV1W1raysoKKBSqcHBwTt37mQL+vj4+JkzZ9j9+sjIyO+//x4as8nJyb/++mtdXd309PTQ0BCDwYiPj1dTU4uLi4PBE/v7+7du3ert7Q0DSczMzFCpVFFRUfZeUR4eHkJCQmzb0M/Pr7OzE/4fEBCgra1tb2/Px8cH48hCF96lS5egmoeEhPz66690On1iYoKXl7exsTE5OXn37t1NTU2XL18+dOgQACAvL2/Dhg0FBQUAAB8fH3l5+e7ubicnJ2lpaQBAaGiogoICAGBoaGjFihXQ7jYzM4Mj/tDpiXpOiw3kN/z0wKeir69PX19fSkrq0aNH7K98fX3l5OSCgoKcnZ1h7PukpCRtbW07OztLS0sDAwNPT8/5phbsXAsJCRkZGdnZ2eno6Dx//pzFYuXl5UlISNjZ2VGp1ISEBGVl5bKyMjMzMyEhofLycnjtpUuXYD8XAFBcXCwlJaWnp2djY/P06dOkpKRNmzbZ2tricLjMzEwFBYWUlBQnJyd/f/+ysjIBAQE9Pb2ZmZmIiAg+Pr74+PgbN24ICQl5e3srKCjIyclFRkZaWFgkJyd7eHjA+TTwBZCRkSEsLBwTE8N2Rfn6+goICLS1tdFotNOnTx85csTR0dHT03N6etrPz2/nzp2enp5nz569fPkyDofz9fXdu3fvnTt3bt++nZmZWVxcLCgoaGxs3NfXNzU1dfLkSU5OTjjAAgBwcnIyMTHx8fHx9/c3MDCoqKjo6uqSlJQ8depUQEBATExMT0+PkZGRmppac3Ozq6vrqlWrsrKy8Hi8hISEv79/UlLSL7/8Ymtra2BgsHfv3ubm5gcPHmzcuPHGjRvT09NhYWG7du1ycHDQ0NDg5+evrKy8cOEC7IYPDw/v3r3b3Nwcj8cLCwuLioqeOHHC0dERGpWIRQVSw8XC2NgY3DRjvm04OTk5ODgIR1HhETKZXFFRkZCQUFJS8nuje+3t7UlJSenp6XBuNpPJ7Ozs7O7uLioqgl7C/v7+pqammpqalpYW9mzkkZGR+TOTR0dHnzx5kp2dPTc3V1FR8fTp04yMjPHx8enp6czMzLi4uMzMTDqd3tzcnJaWlpKSQiQSmUxmVlZWc3Pz3NxcYWFhdXU1DofLz8+vrq4uLCyMjo6GXXUIi8Wqr69PTk4uLy9nqyGVSm1ubobmKp1OT09Pj4+Pb29vHx8fNzU1dXJySk9P9/f35+PjS05OBgBUVVXFx8enpaWNjo5WVFSkp6cnJyf39PRMTk6mpKRkZmb29/fDlLu6uu7du+fq6hoSEsJu4eHh4dDQUB8fn8rKyvHx8ZycnIyMjPr6+pKSkmfPnhUUFNDp9Orq6mfPno2OjqakpDx+/LizszM9Pb2+vr66uvrp06dQMclk8qNHjxISEnp7e7OyskpKSp4+fZqYmFhTU0OhUKqqqpKTk1NTU6WkpNzd3T09PQ0MDPj5+dFS68UGUkPE34CGhoYNGzZAfygOh9PV1f29SZSLlosXLxoZGcH/S0tLDx8+jIINLzaQGiL+BkxOTp4+fdrGxiYyMvLSpUvQXfipC/Vu3L9/X0FBITs7+9mzZ9bW1qmpqZ+6RIiFIDVELHagXxV6PxMSEhoaGj51if4M0E9669YtPz+/+VOgEG8DhUL5CCtekBoiFjuf5cTVz7JSHw4KhTI9PY3UEIFAID4GSA0XKax5fOqyIBD/CJAaLlLYnYLPeFkoArGoQGq4eCEQCFNTU8g2RCA+DkgNFy9UKvUDhYBGIBCvgtQQgUAgAEBqiEAgEBCkhggEAgEAUkMEYj50Oh0tH/7HgtQQgfh/zM7OsvecQfzTQGqIQCAQACA1RCAQCAhSw/cMmiyNQPxNQWr43picnGTv3otAIP52IDV8b4yPj6OlIwjE3xekhggEAgEAUsPPGBaLRSaTaTTapy4IAvH3AKnh58zY2Bjcfw6BQPwhSA0/W9B4DgLxTiA1RCAQCACQGiIQCAQEqSECgUAAgNQQgXgv/OF+XmjDrz/kk7cPUkME4q/CYDD6+voYDMbvncBisfr6+tDk/N9jbm6OTqcjNUQgPgfodDqTyfy955nFYtFotDec8A9naGhoMUwFQ2qIQCAQACA1RCAQCAhSQwQCgQAAqSECgUBAkBoiEJ8hH3NCz+jo6BvG0/9GIDVE/HMZGRkhEAifuhQfCjqd3t/fz2QyP1wWLBaLyWROTU190Fw+Gm+lhmNjY/Hx8VNTU/Dj7Ozsw4cP9fT0cnNzaTTaH74W0LxTxOIETnP71KX4IMCHjkwmf4SMPnQWAAA8Hj87O/uhc3krNYyNjcUw7MGDB/Dj3Nycubk5hmEBAQEzMzNzc3OvvYpMJkdGRkZERJBIpHcqU0tLy7Nnz9jii0Ag/uEQicSPoOx/rIZzc3PKysoYhsnKyrI33k5NTV2+fPnDhw9f3Y27u7sb/jM4OIhhmJaW1pvTf/Xdoq6uvm7duomJibetBAKBQPxl/lgN8/LyNDQ0tLW1lyxZ0t7eDg8+efLkp59+OnLkiLi4+N69e4OCggAAlZWVmpqaRkZG0tLSpaWlnZ2dS5cuFRISioiI8PT0VFdXP3nypLq6en9//4MHDw4fPqysrFxYWAgAYLFYUVFR8vLympqatbW1oqKiP/zwg4+PD9rnG4FAfDT+WA0vXLgQFRX18OFDDMOsra3hwaSkpFWrVllbW/v7+y9fvnzz5s1kMlldXX3jxo21tbWurq5PnjxJTk7+6quvdu3adefOHSMjIwzDtmzZIi4u/vz5cysrq8jIyGXLlklISDAYDDs7uwMHDly9elVeXt7Ly2vnzp3ffffd1atXx8bGPnD1EQgE4v/nD9RwZGSEj49PX1//4sWLS5cuXbduHQ6HAwDEx8dv2bKloaEBAHD27NmVK1d2d3f7+fktW7aMj4/P29t7eHi4v78fwzAnJycAQGBg4FdffRUbGwuTLSoqSkxMXLt27e7du9va2jg4OK5cuQIAaGlp6evr09fXP3DgwIetNwKBQPxf/kANvb29T5069eTJk5SUFDMzsy+//PLatWsAgEePHm3evLmxsREAoKGhwcvLOzk5WVZWFh8ff/78eQzD3NzcBgYGMAxzdnYGANy9e/ebb77JyMgAAMTExHBzc9+4cYOTk5Ofn7+2tnb58uXm5ubsTDU1NQ8ePAj/fy8jVlQqdWRk5K+ng0AgPmPepIbNzc3c3NwXL16EH4OCgr788svdu3f39/f7+PgsXbr07Nmzd+7cUVRULCoqotPpmpqajx8/bm9v37Jli5OT08jIyLfffrtt27bc3Nzr169jGBYcHEyn062srKBcbtmyhZOTc2JiQlpa+n//939DQ0NLSkqGh4dNTEx+/PHH5OTk9zWmTqfTiUTiIpnlw2Aw0D52CMQi5HfVkMFg1NbWRkVFhYWFwcku4eHhUVFRQUFBdXV13d3d4eHhpqam169f7+vrAwCwWKzU1FQVFZVjx47dvHlzdHSUxWL5+flJSkpmZGRYW1ufO3fO1tZ2YGCgsbFRTEzMxsbGxcXl5MmTOTk5XV1dkpKSIiIiJiYmY2NjOTk5+/bt8/X1fb9TOhfJBNHp6Wk0OoRAfCooFMrvBZpEa1EQiHeG/WZdJK9YxNszNTX1ewuQkBoiEH+G6enpqampReJ+QbwXkBoiEH8GKpW6YN0B4u8OUkMEAoEA4B+rhuwODurpIBAIyD9UDQEAg4ODqKeDQHwSpqenW1pa3jWey4dmMaohiUTq7u5ubm5++fJlb29vc3NzT09PS0tLQkJCc3Pze8zlXUNUQkOysrLy4cOHr72WRqPV19dnZ2d/kqh5LBZrYmIiNze3urr6H2Xzslis4eHhgYGBmZmZN5xDIpGGh4dxONwfDgTD1sPj8W1tbR8hkNSbiwE+ekw8AoEwNjaGw+E+XKY0Gg2Pxy8Ip/YXs5vfSn8uqcWohjExMb/++quiouIvv/yybt06RUXFjRs3KikpiYiIeHh4fNqyFRUV6enp6ejoLJiyNDw8PDo6Oj4+Li4uLiws/ElWWLNYrOjo6J9//tnCwuK1J8zNzfX29n4eYYoX4O3tvXz58uDg4Dec09raKiYmpqCg8DabVeLxeDMzM3V19ZaWlvdXzHeju7vbw8Ojt7cXfFyXTlpamri4uJmZ2YLjZDI5ODi4p6fnvefY1NTk5uY2PT392m/ffh/qubm5O3fuJCcn/7liLEY1zM3NjY6OBgAcPXpUSkoKAJCQkJCZmSkpKenq6so+7S2nes2/jRbcUm+4w177FYFAOHbsWHx8/IITaDSakZGRu7s7ACA4OFhaWnp+Om/I9G1u8VfPefMRSUlJW1vb1yZVXFwsJyf36t382mIsaN43mydv81u8TUX+NAQC4ccff7x9+/abC6CjoyMmJrZADV9beEdHx0uXLr2awu+l/I7lff2FCz52dHRYWlp2dHS8a7Lza/R75tIbykyn01VUVOCa2vknE4lEExOTpqamdy3PH/70tbW1ZmZmr1XD0NBQ+GS9DXQ63cnJyd/f/11LCFmMakilUmEEWSUlJbayUCiUrVu36uvrW1paGhoalpWVAQDodPqtW7dUVFTc3NwWRIcdHh6+du1abGzs3NxcWVmZr68vDEcWFxenpaVlZGQEQ07U19fr6+ufPXu2ra3t1ZJUVFTo6elpaGg8e/YMAFBXV7d9+/abN2+yYzhChoaGeHl5ZWRkXrx4ERQUJC8vHxcXZ2ZmFhkZCU9oa2vT1dU1Nzd/+fLlgixIJNLjx49dXFwiIiJmZmYGBgaCg4Ojo6MfP37s5OSUk5MDT0tKStLV1XVwcBgeHgYAEIlELy8vbW3tEydOwDdhX1+fv7+/i4sLBwdHTEwMAIBGoyUmJmpqanp5eY2PjwMA7t69y8HB8eTJEzKZ3N3d7ePjc/369Zqamtf+CjBycmJiorOzc1FRETxSUFBw7do1Pz+/V5fT0Gi02NhYd3f3+/fv02i0mZmZuLi4qqqqBw8eeHl5vXjxAp5WXl7u6uoaEhLyavBOMpmckJDg7OyckpJSXV0NFz6NjY09ffr0+vXr7e3tMNjH/fv3w8PDZ2ZmampqPD09KyoqAABTU1Mw9kdqampQUBA7OOaTJ0+uXLny/Plz+PH8+fMSEhKvdqjn5uYePHhw5coVaAkyGAwhIaGgoKDXRjJ+/vy5h4dHc3Mzg8HIycmBbxcqlVpfX9/b21tTU9Pe3t7a2pqRkQEX8tPp9Pb29vb29traWthpKCwsvHXrFvu1lJOT4+fnB5uIQCCEhoYmJiZOTk5SKJTW1lY8Hg8Tqa2tjYiIgPWl0+nQj1RcXFxVVbVgrSeTyaRSqU1NTcPDwzBSf0dHB7SwOjo6srKyqqur4Q9aWVmZl5c3OjrK/hEbGhqys7Pl5eVhIBX2zQAAmJ2d7erqmpqaolKpOBxubGysrq4O1vFV8Hh8YWFhWVkZdDXMzc1VV1eXlJTM9zxUV1enpaXBijc0NMBgAkQisbi4uLS0dG5ujsViSUtL79u3j0QiVVRU5OTktLe34/H4oqKioqKiBerJYrHodPr4+Dh80qlUanFxcVZW1tsv/XpbNfw4g7ALEj969ChbDVksFj8//759+wICAo4dOwaD3Dg5Odna2jY0NCgrKxsaGs53QwwNDR0+fPi3336bnZ19/vw5Jyfno0ePuru7lZWVa2trb926FRMTk5OTo6amVlpaeuvWLRERkQWRHeLi4tTU1MrKyp48ebJ79+7Hjx9XVlauXLlSVVU1PT19/pnp6enfffedhITE48ePIyIifvjhB3d3dycnp7Vr12ZnZ3d1dWlqajY2NoaHh0tLS0M5Y1NYWOjk5BQcHLx///7g4OD29vY9e/ZwcnL6+/sbGBjs3r17dHQ0MjLSysqqra3t4sWLurq6g4ODFhYWAQEBhYWFV69e1dfXT0tL09fXz8nJCQ8P//HHH5OSklgs1tWrV+3t7SsrKx0dHY8dO9bZ2amkpPTdd9+5u7unp6cbGBg0NDTExMRwcXHV1dW99udISUlxdHR0c3Pbvn376Ojos2fPFBQUGhoaXF1d2YHQ2b+OnZ2dvb19e3u7jo6OnZ1dd3f37t27d+zY4ezsrKWlJS4uPjg4mJKScvbs2dbWVhMTEz09vfl9dhqNZmVl5eHhkZ2dbWRk9OzZM0lJyZMnT9JotBs3bkhISNTV1R07doyDg8Pe3l5ZWXnfvn0XLlxQUFDg4+NrbGyk0+nbt28XFBQ0MTHZv3//8ePHqVRqeHj4+fPnfXx8REVFw8LCWCyWqanpq2o4Oztra2trZmYWGhoqJiZ2//79urq6tWvX8vDwODk5zRcaGo3m6Oh4/fp1X19fKSmpgoKCS5cu7d69u76+PigoyMnJqbq6WkZGZvfu3ebm5mpqatu2bUtKSkpOTt6+fTsPD4+IiEhKSkpgYKCfn5+Pj4+kpGRtba2Pj4+Li4uvr6+FhUV9fb2JicmtW7esra0fPXrk6em5cuXK0tJSAICNjY2FhUVISMjBgwdjY2MTExM3bdrEy8urp6e3a9cub2/v+TWi0+leXl4cHBxwAw8NDY29e/dSqdTY2NgzZ84kJCScOXOmt7fXxcXl5s2bYWFhioqKra2tMzMzly5dOnPmjK6u7o8//viqRWZhYbFp06b4+PiIiIhff/1VSUlJQ0Nj3759Pj4+C+zrzs7O06dPw/1CfHx85ubmTE1Ng4KCLl26dPjw4cHBQSqV6u/vf/78eUVFRRMTEzc3t19++aWoqGh4eNjKyurhw4dWVlaXL18uLS3ds2fPmjVrNDU1paWlN2zYkJOTMzs7e+DAgTNnzsD3xIJn9tdff7WwsJibmzM0NIyLi3Nycrp69epbeofeQQ0ZDAbcDubDCSKLxSIQCGw3wXw1ZDAYWlpaly9fBgCkpqYKCwt3d3fv3LnTysqqvLzczMxMVlYWRhtjY2ZmdvLkSQDA5OSkrKxsTExMe3v7hg0bHBwckpOTh4eHdXR09u3bV1ZWFhUVtWvXrvr6+vmXa2ho2NjYwP91dXWFhYUrKyslJCTy8vIYDMb8RsDhcEJCQjExMXQ6/e7duwICAiQSCYfDrVmzxs/Pz9HRcdu2beXl5SEhIZycnGw7BdYXmq6pqalbtmyxt7dnsVhycnIaGhpMJnN8fJyPjy8rK0tGRsbc3LysrMzNzU1KSsrNzU1SUpLdLLW1tUpKSp6engAAMpl88ODBx48f43A4Tk7OpKQkAEBnZ+f3338fFRVla2u7a9cuGo1ma2u7c+fO/Pz8J0+ebNu2bYG0scs2PDyckZEBLcqkpKS4uLhvv/02MDCwsLCws7Nz/smlpaU7duyAJnNycvKWLVsqKiqUlZVPnjzJYDAqKipERUVLS0slJCSOHDkSGRlpa2vLz88/P7w5gUAQEBCQkpJKTU2F6nznzh1ZWVkAwOXLl1NSUlgslpmZ2ZEjRxgMRlRU1DfffNPe3j48PHzgwIH09HQGg7Fp0yYXFxdoo23cuDEsLExUVDQvLw8A4OXltXbt2v7+fktLy1fVMDo6mpubGy63t7GxERERmZ6eFhcXDwoKWjDomZKSsmHDhoSEhLy8PE5OzrNnz87OzmprawsLC1+7dm18fJzJZJqZmUlKSpLJZAqFIi0tLSsrOzo6umvXrvPnz/f19d27d2/btm1hYWHZ2dkcHBxXr16VlJTU19evqKiorKwsKChYsWIFbOHBwcGSkpJffvmlvLw8Pz9/z549ra2tAIC7d+/CYHp79uyxtbWlUCiWlpYqKioLHviOjg4uLq6oqCgWi3Xnzh0ZGRkSiWRubn7w4MHS0tKurq5nz57t2bPnwYMHT58+/eGHH/z9/a2srExMTMhkMplMVlJScnFxmX8zAACGhoZ27Nhx//790dFRTk5OLy8vEokUEhKyc+fOycnJ+bnHxMQICQnl5uaWl5c3Nze7u7vLyclRqVQymXzgwAEbG5vbt2+rqKhMT093dnampqZWVFRs3br15cuXXl5eBw4cyM/P9/X1XbNmTV5enp6eno2NDZFIbGpq4uHhycvLm52dPXXqFDvy9HzweLyAgICVldXw8PDPP/989+7durq6gYGBt5Ssd+gp0+l0GIvhg5qH4+Pj7IkvSkpKMjIy7Nz379/v5uYGAEhNTT106FBjYyMHB4e1tXV0dPSzZ8/6+voWDFHZ2trq6+sDAGZmZpSUlOAzn5iYqK2tvWHDBicnJyUlpX379sXHx0dFReXm5i5w1qqpqRkZGcH/b9++LSoqWlZWJisrW1lZCf6vGUskEg8cOPD48WMAQEBAgLy8PKzI+vXrAwICNDU1RURE4uLioqOjMzIyFjyKkZGRCgoKoaGhoqKiUOvV1NTs7e0BAJOTk0JCQk+ePBEVFZWTk4uOjo6Nja2trb1w4YKQkBA7BRqNJioqCgcQqFSqhIREcnLy4ODg8uXLoQ07Nja2fft2aLzs2bMHAGBkZLRp06b79+9HR0cnJSWxO0rzYbFYoaGhJ0+evHv37t69eyMiIqanp729vaWlpVevXr3AQ/fgwYN169ZBf39ZWdmWLVuePXumrq5ubGwMAKitrT18+HBpaenOnTsPHjxoZWUVHBycl5e3oLNcUlJiZma2f//+Q4cOdXR0DA4O7tq1KyUlxdXVFeqslZUVTDA2Nvann37q7++fmpqSkpLKzs6mUqmrVq0KDAwEAExMTPDw8Dg4OKxfvx52CTMzM9evX9/c3GxjYyMhIbFgmNjNzY2Hhwc2Qm5uLi8v7/j4uLS0NHQ4zMfV1fX777+PiIiIjY319vZOS0sDADx9+hTDMBj+HQBgb29vamoK/zc3N5eQkMDj8YKCgnfv3gUA3Lt37+eff/bz84uOjvb09CwsLCwqKpKTk+Pn57e0tBwZGbGzs+Pn5xcUFIyPjx8bG7tw4UJra6uzs/PevXuhL6itrY2Xl/f58+dycnIpKSkAAG9vby0trQU3P5PJPHz4cHFxMbzHlJSUyGRyc3OzmpoaDw+PjY2Ng4PD6tWr3d3dQ0NDr127VldXx8XFxXaVQnttQfUpFIqNjU1tbS0Oh9u3bx9sn/r6etiDmX/nvHz5Ultbe+/evXJyctnZ2cLCwioqKvBbOzs7TU1NVVVVAwMD9iVVVVX8/PwvX748fvw4Pz+/m5tbSEhIQEDA0NDQ+fPn2bqso6Nz/vz5qKiomzdvvlaFSCSSmppaeHg4AMDR0XHnzp1iYmLR0dFvuRfYYvQbQqhUqoyMjJiYGHxmCATCmjVrrKys6HT606dPt2/f3traeuLECQ0NjbGxsampqVdHS+Pi4nh5ebu7u2NiYlasWHH//v3k5OScnBwKhWJnZ3fu3DlfX9+tW7eWl5czmcxXnQtXr17duXNnW1vbzMyMhoaGv79/Q0PDqlWrIiIiFtiGfX19nJyct27dIpPJXl5eIiIiNBptbGxs5cqVHh4eDx8+3LVrV11dHZPJbG9vn//DUCiUw4cPHz9+fGhoSFhY2MzMjEwmS0tLGxgY0Gi0iYkJLi6uwsJCbW1taWlpHA43NTUFY/ysWbMmNjYWj8fjcDgCgWBgYCAkJARdQsuWLQsMDCSTyeLi4tbW1iQSqby8XEREpKGhwdLScsuWLUQiMSQkZOvWrXV1dSwWq7u7m0QiZWRkXL9+fb4jhkqlbtmyxdraGo/H8/DweHt7JycnV1ZWTk1Nqaio6OjozG+rnp6eHTt2+Pv7z83NxcXFycnJDQ8PKykpqampMRiMyspKQUHB/Px8fX19Q0NDeMmCt8Lo6Gh0dDQej29sbBQUFExISAAAmJqarl69OiUlhcFgMBgMY2NjNTU1Op0eERGxZMmSzs7OyclJPj6+hw8fUqnU7777zsPDg0KhJCYmKisr9/T08PPzP3jwgE6n37x5U0lJiUAgnD59Gpp+87NOTEzctm1bSUkJi8UKCgqSlpamUCgiIiKhoaELbomUlBQODo7s7Oz5xXZ1dT1z5gwfHx98TdrZ2RkYGFAoFBwOp6qqGhcXNz4+zsvLm5iYCADIy8vbtGkTFCkAAIvFiouLGxsbi4uLW7NmTXZ2dlFR0cuXLw0MDE6fPv3ixYvdu3eXlJQ8f/6cg4MDenizs7P37dvX1NR04MABONjo4eGhqqq64F0+MDCwc+fO0NBQMpl87do1CQmJ0dHR+vr6zs7O58+fS0hIaGlpCQgIzPf6HTx48NSpU2QyeXBwUEBAwM7ObkH1CQSCpKRkamoqAAA6HwAAGRkZnJycC16oFRUVVVVVDQ0NqqqqkpKSJiYm8vLy8JE5e/bs9evXHRwc+Pn5x8bG6HQ6jUYrLy/fuXPn6OjoxYsXpaSkBgYG2Enp6OhYWVnB2uXl5a1bt05ZWbmmpoZEIqWmpi4YLZidnYXPEYFAaGpq6u/vt7CwkJKSWtBr/D0Wrxrm5OQYGRmdOHEC/uTx8fGampqGhoZNTU29vb3a2tp+fn5dXV3QJ3Xs2LGsrKwFr4vh4WFlZWVxcXEXF5c9e/acP3/ez89PWlr60qVL1tbW0K98+fJlISEhaWlpHx+fBQWYnJy0trbW1ta2trb29PTE4/EBAQHbtm3T1dWFvSo2VCrV2dlZSEjo3r17+vr6fHx8+fn5RCJRTU1NRkamu7vbyspKWFhYWlraw8NjvmQzmcyoqKj9+/eb7g+mRwAAIABJREFUm5ubmppKSkqGhoYeOHCAj4+vuLgY+vKvXLlSXl6urKwsISEhKyubmZnJZDJv3rwpIiIiJSWloKBQVFTU29t7/PhxcXFxNzc3PT09RUXF7u7uiooKeXl5XV1dXV3d1NRUFouVnp7Ow8Nz4cKF3t5eGxsbMTGx48eP29vbDw0NSUhI2NnZzVdqJpPp4OAgLCxsYGBw8ODBCxcuODs7y8vL29raWlpaQl/+fKKjow8dOnTx4sWTJ0+WlpbCx1VOTq69vb2jo+O3335zcnIqKyuTkZFRV1c3NzePioqaf/no6KiBgcGFCxdcXV29vLzgXZ6RkbFz5044qPry5UtZWdnffvutpKTE3t5+x44daWlpU1NTCgoKpqamQ0NDgoKCwsLCZ8+etbe3h53K2NhYdXX1wMBAAwOD0tLS0dHRY8eOiYmJLfCTdnV1WVhYaGlpRUREaGtrV1dXV1dXc3FxaWlpzX8sAQAMBuPChQv8/PwXLlwwNjbOzs4+c+aMv78/nU7X1dWVlZWdnJx0dXVds2aNvr7+uXPngoODmUxmRkbGli1bLl++jMPhaDSamZmZkJCQubn5qVOnCgoKlJWV7927FxwcbGdnFxQUdPz48dTUVHNz8/j4+MjIyJUrV3p7e9PpdFNTU01NzfDw8DNnzkRGRr548WLHjh1nz55lMpkBAQEiIiK1tbXzizo3N2dsbCwgIGBubi4jIyMgIJCbm+vh4eHo6PjkyRNHR8fBwUFra+tjx475+fk5OTm1tbWlpKRwc3NraGiYm5vz8PBoaGiwXRnwySovL9+4caOHh0dGRgYXF5eLiwu8gTk5OeE4GxsvLy99ff3a2lpLS0s/P7/R0VFpaemQkJDHjx+rq6uPjIw0NDTw8fGZmpqGhobGxcUlJCRs3bo1MTGxsbFRWFhYS0vLz8/P09OTSCTCJ+vBgwcwMKioqOiZM2cAALdu3ZKVlV3wYqupqeHk5FRTUysvL3dwcEhPT3dycgoKCvrb24ZQNVgsFpVKZTKZ0JnNYDDYFWO7t6Gn4/ccpXCWNYvFotFocKyNQqEsMNBIJBKNRnut7T03N8ceWIQp0On01zpPqVQqlUql/xfoV2a/sclkMolEotPpr86wodFoMAsajQYrC1+YcOtumAIc4SWRSGx39dzc3OzsLJlMnt8OsF5UKhW2BpFIrKiomD8VnMFgsB0RsN3odHpqaqq0tHR/f//86rDLT6FQ2LUeGBgoLi7+vb0cx8bGioqKoAsJ/lLQpoNOZ1gRJpPZ0tIyODi4oCngV9B9xj6SnZ3t4ODA/hamNjMz09fXx2KxpqamYH3hZrtkMrmvr6+4uHi+s6+lpaWgoACOj42Pj798+bKlpeVVzwCTySwpKUlMTIRndnZ25uXlFRcXvxoynclk1tXVZWdnj4yMzM7OVlZWwt+ORCIVFxfPzMxcvnxZQUEhOzub/cp88eJFfn5+SUkJ27lWWVmZmZn54sULBoNRU1OTm5sL0yGTyYWFhbm5ub29vXAmPxyWhb9menp6UFAQfDeMjIwUFRVVVlbCuO4FBQVNTU0L2nN6erqgoKC6urq3t7e8vLyjo6OnpycmJiYjIwOOP5BIpNLS0qysrPb2dphFT09PZmbm8PBwd3d3SUnJfDVksVhNTU15eXktLS0tLS15eXlVVVUUCmV0dLSwsLC+vn5+7sPDwwEBAdeuXYNzPwAA/f39t2/fDgwMZKfZ3d2dlZVVXFwM11bk5eVBx/3Q0FBubi70nMLbvrS0FI49zs3NXb16NTc3l0QiycnJQd/UfHp6egoLC6uqqoaGhqqqqp4/f97Y2Pj2E2wXrxrO589NZ3tX3pzCu85bfJtR+Dd/xa71HxbstfO53jDJa8FXOTk5cODyzZe/PQva6k9MeaNSqXV1dQ4ODtA19lcK8Id5vblU7zo/9NKlS2fPnmV/fHXa5luW6g383lWvnWb4lon84S/+2mdw/iVvuF3fvppvbp+ysrJLly7R6fT+/v6wsLAFzoG/rgB/DzVE/NPIyMiAg2ZUKvWDjtq9X1paWmCH/fcmLSH+HGNjYwYGBjIyMnBKxgfaSwOpIWIxQiAQenp6YJf8b6SGPT09zc3NQ0NDMzMzf6NiL35oNFpqauqfWAbzTiA1RCAQCACQGr53Fr9FwPq/vOG0j1kqMK9gf3jORyvSJ+FdPZWI98VHUkM4JtDU1NTZ2fmhN9YhkUhDQ0PzPQtDQ0Ph4eFwPUNycvL8daxvZnZ2NiEhAQ6uTU5Otre3FxYWFhcXBwUFsVcQg/8O+MLJU5/w9h0YGAgPD4+NjX1z3Mb5YxpvLm1fX9/9+/cXTN14M3Col0QifaB2gGWmUqnl5eWFhYVvOXPitTCZTDiXAIfD1dTULKodt1ksVnZ2Nmz5qampyclJAoEwOTn5e60K22RkZGR8fPyvtMl84ESCT3U/E4nEsbGx35u98IH4eLYhmUw2NDTU0tL60DWEy4rnR/5obGzcuXOnsbExlUo1Nzffvn17V1fX2ySVnJysqKgI16Ly8fF5eHgICAhoaWlt27aNPfODfSYvL++CeYjvyl+882pra7m5uWVlZd8Q5g/8d8kdnN7x5hyrqqo4OTnnxzL5Q/B4vIKCQmxs7NtfwgYulnhz+CZY4M7Ozj179oiJib25pm+mt7f3xIkTqampt2/f5uTkzMjIeHOmAAAKhTIyMvIR9smLiYkREBCAazDu379/4sQJcXHxGzduvHb0ABavr69PXl6eg4MDRgb56ypWWFior6//EV4Sry1qSkrKpk2bLCwsfq+1x8fH37tS/4EaUv8/9t47qqokax/u1TPvdLLb6WDCBEoSBSQjKJIkBwHJEiVIziBcckaiZAWRJDmD5BwkSA6Sc87pEi/3nt8fe81ZfGjbdJh3et6v9x8s7r1VdarqVO2q2rWfZ+/t5eXlFRYW7u/vHxwcbG9v9/X1zc/Pd3d3w0Ds6OjIyMgAPpiDg4OpqampqamFhQXUx2d3d3djYwM+bm1tHcEzHmFFXV9fP8wM+NHWwpJ1+JsjybBY7Pv374/sj4yMjMDvobu7m5aW9pjasL6+/t27dwiCoDwROTk5paWlN2/ePKINl5eXKysrUcgXyhl1zJlzpLZoA3/t+9bR0eHm5v7Fh5qamvLw8Pzcr4cf+ujRIxSs/emUIDs7OyUlJUdcF48p2dnZV65c+QRR7uF2mZmZUVJSfshU+GmPlsOyvr4eEhLS2dk5OzvLzc0NEIuPFoJ+k5KSIiwsfMwLzQ+33sd0rxkaGmJmZj68strZ2aHYwQ8rhpaTkZHBzs5+xGP85+QXB0lbW5ujo+ORCftR+bSH2a/Ke/ijgICAmZnZR8vJzc2Vl5f/VaUdRz6lDXt6evT09JydnZWUlERFRR0cHOzs7FhZWdnY2G7cuFFQUBATE6Ovr4/BYMTFxZ89e7awsGBnZ8fExBQQELC/v19UVJSamorFYq2srLS1tcPCwrS1tYOCgiorK1VVVS0sLBQVFTk5Of39/UFXRkVFPXr0SElJCYPBhIWFAc9PVFSUmpqajY2Nqakp+GQaGRk9ePAAcLIJCQkyMjLe3t46OjpKSkohISEbGxsvX740NTUFpF1HR4eXl5eRkREFBYW5uTmCIN3d3YyMjG1tbX5+fgDSmJ6e1tfX19fXB9qrw7K7uwtDH5Ae6ACipaWVk5MzMDDQ1tZua2tbXl6Oi4uzs7OD7b2Xl5ehoaGFhcX8/DyBQBgbG3N3d3dwcHB1dQ0ODt7b24uNjbWzszM3Nx8cHNzY2PD19TUyMrK2tu7v78fhcIANMDAwAM6oiIgIZWVlTU3N3t7e+fn5iIgIS0vLgIAAT0/Pzs5OIN1SU1NTUlKqrKwEUhBvb28lJaVXr16h2/CpqamAgAAbGxs3NzfAzJ05c+bFixepqakYDKa6unptbS0hIQFwKQiC9Pf3W1paamhoUFNTu7m5TUxMqKurm5iYTExMQH1ev34NJU9MTDg7OysrKwMMvLOz09HRsb6+vqenJyAgID093dTU1MDAoK+vLyYmRlVVtaGhAUGQ9fX1V69eGRgYmJubo+sfBoP58ssvMzIysFjs9PS0m5ubkpJSaGjo4d3i/Py8r6+vsbHx3bt3JSUlYdkoLS1VVVV1d3eHyhcVFWlra+vq6oKbS1tbm6mpqbGxMdCSA9w7NjZ2eHg4MzOzs7NzYmJCWFg4ODg4Ojo6MjISYDCbm5svXrwwNzcvLCxED4zW1tbffPNNdXV1VlaWr68vgOri4+MDAwOrqqpSUlJKS0vfvHnj5+dXVVUFFW5vb/fz84uIiIC6dXV1BQYGBgYGHmZxb2pqsra2dnV1BY6v169f09DQ5Ofno/YcZ2dngPG2t7e/ffu2rq7u2bNnSUlJKBLj/fv3ERERZmZmDAwMoEaxWGxcXJyXl1dKSsrBwUFvb29xcfH79+8zMzOjo6Nhydnb28vIyPDz80O9TXNycnx8fNLT0zc3N/v7+2tra6E34G0C6Ht0dLShoWFqaiorKysmJuYIGqS0tDQ4OBhw5UNDQ42NjaOjo2/fvk1KSkLnV1FRkZeXFwpw3NvbS01N9fLyKioqgkmXkZERFhbGwsISHR0NaQoKCry8vKKiomDfYGxs/OOPP4LL9+bm5uvXrwMCAuDGeXt7OzEx0cfHp7q6+tfu4j+uDbe3t9fW1jw8PMjIyBAEKSws/PHHH3Nyctrb29nY2CQlJevq6lJTU9nY2Kqrq3d2duLj4//xj3+8efOmtbX166+/BtAVLS0tMzMzgiD6+vpGRkZ9fX0CAgJUVFT9/f1cXFwnT57MzMyMioq6cOFCc3NzY2MjCwtLa2trcnLy2bNns7OzwV2+qanpzJkz1NTUBgYG6enp6enpOTk5z58/JyMja2tr6+vrIyIikpSULC8vNzMz++GHHxoaGoAmZGJioqWlRVJSsqCgoKqqioODAxihu7q66OnpBwcHMzIyvv7665SUlK2trevXrzs5OX3iCC8jI8PPzw+di8fjycnJOTk5i4uLlZSU2NnZd3d3U1NTT58+PTIy4uDgoKCg0NLS4urqCr71q6urIiIin332mZycnIODg7u7O0CyZGRklJWVQ0JCREREGhoanj59mp+fj8FgdHV1m5qapKWlFRUV+/v7fXx8iouL6enppaSktre3o6KivvvuOz4+PiMjo/z8fF9f38ePH5eUlJiamkZFRZmYmFy7di0xMTEwMPD8+fPgrI/H4zU0NDQ1NRsaGnR0dN69e8fDw3Pz5s3ExMTk5OTvv//e1dV1b2/PwsLi+vXrS0tLjY2NgHUvKCggJiZ2c3Pb2NggISHh5uYGCkJaWlpAjODx+KSkpICAgPDwcHJy8tra2s7OzrNnzwJtIhUVFTs7u5OT061bt8jIyJydnWVlZZmYmEZGRiIiIhQUFOrr6+Xl5SsrK2EOqKioEBERxcbG9vX1ATarqKiIj4/PxsYG1suBgYGHDx8+f/48JyeHhoZGTU0Nj8fHxMRoampWVVUBKDA3N/f+/fsVFRW+vr7Pnz8vKip69OgRAMKioqLs7Oy++eYbbm5uYWFhoHIIDAxcWlpiYWERFRV99uwZKSnp48eP9/b2DA0NY2JiCgoKWFhYYDxPTEywsrL+8MMPjo6Or169unz5sqOj497enra2NuAFhYWFz58/7+DgYGBgcP78+ZycnN7eXiUlpXfv3jk6OsrLy9fU1CgoKFRVVQUHB/v7+8PQSklJUVRULCsrs7e3Z2Nj6+josLOzO3/+vK6uLpxLEARxcnJiYWEZHh52dXU9f/68oKCgvb09CwsLEHlFREQYGhqGhoYCCwkgc3R1dYOCglpaWsTFxd3d3ePj46moqJiZma2srFhZWc3NzfF4vL29vYeHR1VVFScnZ3Z2dlBQkJOTU1NTk4iISGNjo4qKCgUFRU9Pz9u3bx8/fuzm5sbBwVFdXZ2SkkJBQUFHR2dlZcXHxycnJ4eigAMCAiwsLExNTVlYWJqbm9PS0iClg4MDDw+PsrIyLPYWFhaFhYW8vLzp6emwF/Hw8DA2NpaQkJidndXV1X369KmLi8u3334LPZ+UlKStrd3U1CQnJycjI9Pb28vDw3PixAlbW9u2trYnT54UFxfn5uaysbHV19d7eHgEBQWVlpZKSEgcQTH/Rm14cHCAx+NBraSlpXl4eGhra+NwuL29PTo6OoD0lpSU0NPTw0Z6amrqp59+sra2Pjg44OXl9fLyysvL4+PjY2Zmbm5utrOzA9yomZkZoP21tbWFhYURBFlcXLx7925paWlRUdGNGzdmZmaSkpI4ODjQIycWi717966npydqMEpOTsZgMBcvXqyurkYQhJ+fH5hLEARhZWUNCAiora0VEhIaHR3V19cHDhsEQQwMDIBZpKuri46ODthWODk5PT09+/r6LCwsPs0OLyMjgxKTHBwcAJ0BgiBFRUU0NDQIggwNDdHT04+MjISGhpKQkBgYGOTk5KCtsLW1ZWRkXFxcXF1dvXTpkrS0dGVlpampqaysrLe3NwMDg6amZlFRUVNT07Vr1zQ0NEpKSiwtLdXV1dfW1pqamnJycjg5Oeno6BAEaW5uvnnz5ujoKOD/bt26BSfZ7e3tubk5PT09Tk7Og4MDLBZ769YtIPNAEOTJkyfXrl2zt7cHbgIlJSXINTc3R09PDx2YkZEhLCw8OztraGj48OFDyAhkhQiCvH79mpWVFYvFhoeHH4YYz87OlpSU5OTkkJOTAyu4lJSUl5fX3t4eLy8v2BNiYmKYmJj29vZ6e3u//vrr4uLiqKgoUlLSoKAgQFkhCEIgEHx9fYGwKyUlhZGRETZTr169IiIiAgIx0KewHzQwMGBjYxsfH79165asrGxPT094eDgVFZWvry8dHZ2Tk1NVVdXMzIyenh7UamxsbGlpKSEhgYSEpLu7e2NjY3FxkZWVNSMjY2Njg5ubOyEhAY/HQzNfvnxJTEwM3GLc3Nzw6nE4nIiICC8vLxaLPTg4EBcX19DQ2N7eNjIygis1RUVFOTm5nZ0dLBbLxcWlqqqqpaUlLi7e1tYWERHBwsKSlpZGREQUGhr67t072MgcHBzw8PDAWNrf3yciItLU1ExNTRUREenr65uamoJOdnJyYmRkXF5eHhsbu3Tp0ps3bw4ODjQ0NDAYzPDwMCMjY01NDYFAiI+PFxIS2t7eTk5OvnPnDuzF0tLSvv/++5KSEgUFBScnp52dHV9fX25u7vfv37OwsMBU5eLi0tbWpqenB/fm3Nzc/f19WPYGBgbW19eLiooKCgpu3LgRHR0NJBRubm47Ozs5OTlAFwL1bGlpqaqqioiI+Pzzz4Fo+cqVK48fP97a2qqqqqKnp3/79i09Pb2amlpRURE3N7eUlJSurq6MjAyEScnJyQGL1v7+/tbWFg8PT0xMzNbWFi0tLWwSu7u7T5w4kZCQ4Orqqqqqurm5GRgYePPmzYSEhPT0dGpq6rCwMGlpaTU1NdhB/zF7Q5DV1VUWFhYVFZWIiAhYnNfW1hgYGEAbVlVVnTp1CrY/g4ODP/zwA1A9BwYG3rhxQ0JCoqury8LC4s6dO8+fPwe9YGJi8uDBg/39fQ0NDQkJCRijvLy85eXlm5ubjx49srCw8PPzgw05yNLSkpiYWHJyMoIgCwsLYmJiXl5eb9++paWlBSIQPj4+mJwHBwfMzMyVlZWVlZVCQkKDg4MKCgoo1YqGhgbEeQBtCEeSoKAgdnZ2CwuLw4DHj/o3yMnJKSoqwseDgwMKCgog3SosLIT9LwzKgYGB8fHxpKQkPT09YmJioBdEEMTOzo6NjW1ra2tzc/PUqVMGBgaDg4NdXV0LCwuLi4vp6ena2toXLlzQ09NjYmKytLTs7e3t6+tbXFzMzs4WFBTMzMyUk5NjYmJCEOTdu3foIoQgyKVLlw7Hr9DV1eXj4zs4OABOqqysLARB9vb2BgYGAgICxMTEyMjIWltbdXR07O3tEQSZnZ1lYGAoLi5GECQrK0tAQGBkZERcXBzFlikqKkJLp6enmZmZXV1dra2tYS1BEGR7e1tPT09OTq6uro6NjQ30jpycnJeX18HBAT8/P9DAxMXFASFjb2/vt99+m5+fv7u7GxYWJi8vf/bsWcgFr4OFhQVBkODg4MuXL4OZLD8/n4SEBFZTAwMDaWlpSGxmZqaqqjo5OXnlyhVZWdmYmJiIiIiCgoKJiYnExEQ5OblTp065uro+evQoJSUF7Z+kpCRubm44bW1ubnJxceXm5m5sbPDz8wO9eWNjIycnp7u7++nTp4OCgl6+fBkbG4veqktKSgLlIoIgGRkZQOPm6OgIw1tOTg5lSFVUVAT9wsHBAQfw3Nzcubk5X1/f+/fvk5OTQ8r9/f0LFy6g91RgfsnJyREUFDxMZerk5MTExLS+vr60tERHRwcE3QYGBk+fPs3JyaGkpAS9mZmZKSoqury8bGVlxcnJCWcdIDIoLi5+/PgxUOQnJCSIiYmVlZVdvnxZWVnZ2Ng4LCwMMNFaWlqXL1/m4+ObmJjIz8+/f//+5ubmu3fvjIyMPDw8qKioEhISgCemvLwcQZDS0lJeXl5Yq3A43IsXLwwNDT08PK5evQo3aVxcXMB1BsfKvLy869evKygoYDAYLy8vMMGrqamhLeXl5Q0MDIRZJioqGhcXt7i4+MUXXwAD0MbGBjMzc1BQ0LNnz2CImpiYnD17VktLy9bWNjExEWDpysrK5OTkDx8+/LVXQJ/Shmtra0xMTNLS0pqamjo6On19fbW1tV9++aWUlNTk5OTKyoqwsLC4uHh+fr62traxsTG8v66urr/97W+mpqYIghQUFHzxxRd5eXkIgmCxWHFx8StXroyMjACh2/r6+uTkJAsLS2xsLA6HExcXFxAQcHV1ff36NWoJ7u3tpaenf/r0KYFA6Ozs/Oqrr16+fBkQEPDPf/4T6NW4uLjg9OHg4GBoaLi1tZWZmUlFRTU2NlZQUABLcVZW1oULFx49eoTH46urq69cuQLkSFNTUzdv3hQXF19ZWQG+KZSwHgRVfwICAjQ0NDCLdnd3SUhIzM3NCQRCfn7+jRs31tfX37x5c/78+ZaWlvDwcOB3ERISAjVNIBCsrKwYGBjAjGhhYcHExPT27duenp7W1taoqCjoH1lZWWdnZxkZGV5eXuBn7+3ttba2Zmdnr6uro6WlpaKiOjg4SEtLIyEhmZmZgbppamrS0tK2trb29PRMTk5qaWndvXt3Z2dnYWGBnZ09KiqKQCAsLi4+f/58bm5udXWVk5Ozurr68ePHPDw8LS0tc3NzbGxsDx48qKurU1NTIyYmnp2djYyMJCIiAurDU6dO2djYgKnezc3t66+/Bl4W6J/5+flvv/3W1tY2IyPj0qVLmZmZKysrLCwsnp6eOzs7XFxc+vr6BAIhOjqajo4Oi8X29PR89dVXubm5kZGRMFK5ubmBpxZBkGfPnlFRUTU0NDQ2Nl6/fj01NXV/f9/Dw0NVVRXUTXh4+KlTp968edPZ2Xnz5k1RUdHV1VVFRUUuLi4Ye6urq/Hx8WB+cnBwePTokbq6uqKiIhaLXVlZgZqwsLDAWrKyssLMzJyamrq+vg6DcG9vz9LS0tbWtru7m4SEBKbx6uoq6toiJiZGR0cHWgZILZmZmUEvEAgEAwMDOTm57e3tzs5OUVHR6upqc3NzJiYmYByYmZlpaWkpKSnB4/HGxsa8vLyQ6/79+6Kiong8HovFgvklMTHx1KlTaLQJPB5vbW1NTU29sLAwOTlJQUEBJ2iIYDE+Pk5DQ/Pq1av9/X0bGxtQmhkZGWfOnHn79i0ej4+OjhYSEpqYmJCWlvb29iYQCDExMTw8PO3t7devX0eXit3dXThJdHV1wYkwLy+PjIyss7NTXV0dVlwODo7IyMj19XV6evrQ0FAEQQoLC9nZ2YF4dW5ujpycvKCgYG1t7dy5c3Fxcfv7+xwcHNCNzc3NNDQ0DQ0NKNUjCJChTU5OAq+Hrq7urVu31tbWpqamiImJX758ubu7CxoASD14eXl7e3udnZ0lJCSA242cnBzGEhaLnZmZgQW4qKiImJi4rKwsLS3to7ywH5Wf1YZ4PD4nJ0deXt7e3h54z8XFxRsbG/Pz81NSUkBbzc3NRUdHx8fH5+bmorei6+vrMTExKNNGWFgYJG5razM2Nra3t4+MjHz69OmTJ0/KysqwWKyrq6uNjU1bWxs7O7ukpKSamhodHZ2QkBBMgKioKEVFRS0trf7+/r29PX9/fx0dnfT0dBMTE09Pz/39fQEBgbt375qamsbExGxsbGCxWG9vbxkZmeTkZGC+kpGRATONmppaQ0ODv7//gwcPYmJi4MClra3t6emJIEhpaamGhsaH93E4HC47O1tJSUlVVRUsXOnp6Q8ePDAzMxsaGhocHNTU1PT39/f09Hzw4EFgYGBcXJy0tLS2tvbLly/hDNjf329qavrw4UOIOzo/P29mZqalpWVjY9PT05OdnX3v3r2HDx+Gh4dvbm4ODAyYmprq6emZmpo2NzcPDQ1paWk5Ozvb2dnp6+tnZWW5uLjIyMg8e/YMTOxLS0vW1tZwCZOUlGRsbKyiolJVVbWxsWFvb6+jozM2NobD4Xx8fO7duycrK/vq1StYEnh4eMLCwnA4XExMDBkZmaKioouLi5KSEtjFLSwsbty4YW9vDztK2ByVlZVxcXHBRoDwL/YdICsLDAw0NDT08vKKj4+XlpY2NDSsqKjg4ODQ0NAYGhry9vYWExNLS0ubmpqSkJAICgpSVFQE0+eTJ09Q43pjYyMPD4+Kisr6+npUVBQXF5eZmZmVlRWMJQKBsLW15enpSU9Pb2xsjMFg2NnZExISZmZmhISEODk5+fn5o6OjX758eevWrSdPnpiZmTU2NoK1Gkgk+/r6lJWVKSgoQkNDDw4OcnJygJ+to6ODn59fQEBAQEA1lBOGAAAgAElEQVQgICAAbCaxsbFUVFQCAgIPHjxA94bFxcXXr1/X1NSENNbW1lxcXKgDgLe395kzZ/j5+RUUFEpKSggEwtzcHC8vLxcXl6Ki4rNnz0pLS3l4eGxtbZWVlVE2ipGRkfv376uoqKioqPj4+MzNzRkbG1+4cAEl9y8vL+fi4qKjo7O3t7e1tSUlJcVgMFgsFoPBMDEx9fb2hoeHX79+XVpaWl1d/fr168AAZm5uLigoaGJioq6uXlJSUltbS0NDo6KiMjc3B2bo0tLS58+f09DQKCsrq6ur19fX8/HxWVlZ+fv7m5qaDg0NWVhYXLhwISoqytbW9ubNm1paWoyMjDo6Ok1NTWRkZPfv3ycQCI2NjTQ0NKBksVishISEuLj448ePKSgotLW1gdlTQUFhc3MTGDATEhKSk5Pp6Oi0tbUfPXpUVlY2MjJy9+5dPj4+2OqOjY3x8PDcunVLR0dHQEAATDdFRUWcnJxGRkYSEhKhoaEEAqGoqIiUlNTY2Hhubs7U1JSVlVVDQ8PS0rK5uRmiQVhYWLx69WpgYICFhQW98fvt2nB7e5udnR0IHREE8fLyEhcX/6hx7TjRacE7FO7mtre3CQQCUEvBT8BmbmhoCOlramquX78Ox7Hd3V0cDre9vY1eLKJqFwrk4eGJjIxESbegWBwOd5i3Csbrzs4OkCbt7++jZyWIN4L8y1PhiFcEOI3D06FMcNmFOFZAugURkaCewLi1sbEBOxEoFgi7wBSC9hUWi0XtZRsbG4eD/MI2YXt7G77B4XDQuoODg62tLXgQFotFScOgIZBlb28PWgf8V5AMKrm8vLy8vHyYEAyi8EBlNjY28Hg8NBYSrK2twXPhJwRBkpOTbW1tP3Ri2NzcBEMzUIRBS4FwDBq+s7MDLPDQGzs7O9vb26urq6urq4e9VWAkoGNsfX19dXX1wzhNq6ur4N0FFGcIgoAHNbCmHxwcrK2twU0COmDAeX5vbw/WSywWC8/CYrGbm5tQpbW1tSMubGBbhLC/aL9tbW2htvmQkBA0iAIejwd3iOXl5cPXrPv7+52dnZ2dnVC38fHxoqIi2Mugz1pZWSkqKkJ1LrzKw/Xf2NjY3t7e2NjY2NgAewuQ/W1sbMC8GBkZGR4e3t3dhV8hY0dHB2qWRdsObYFXgyDI8PAwxGna39/v7u7Ozc1taGiAMbC1tbW9vQ3jpKura2hoaGtra2hoaG5ubmJiYnBwENjn5ubmwPkBQZClpaWysrLx8fGNjY3Ozs7l5eWtra2RkRGYDlgsFuZdc3NzRkZGd3c31GFzc7OysrK2thZuund3d6urq8GNfG1tDSYvHPXQoxuBQBgdHYXbczweX1VV1dDQAJ58c3NzWVlZaOyzkZGRj3omfVQ+dVIOCAiQlJT08/Pz8fHR0NCoq6s7ZqEfyi86/jx//pybm7uhoeHt27cWFhYfjRn4YSFNTU1nz55Fo8B8qMs+UZ/4+HhTU1MwYP/cUz4s4Vd5MP27YWS/36XrmCUsLS3FxcWpqqp+SPx1nOy/qnqfSPa/hov4xfe+trZWXV0NpOXol0pKShCoAM3y6QrDr8dJc/zvj/PrceQ/BUE5jvyGAXxM+ZQ2JBAIZWVlqampaWlpoJX/fX20t7cXHh4eEhISEhKSlZW1trZ2nGelpaVpaGi8fPny116lb29ve3h4WFtbg03nz/zu/wzS2toqLi4eERGB/Jf3FRxKfmcTwFwlIyMD4QpAampqmJmZmZmZwdXhL/lvlF+BzPv3Lc5osXCKOfLlJ3Jtbm7C+ff49LYgKJnzcR70l8Bh8zh7mT+57O7uzs3NfTRK8vEFDIJHUJhLS0sDAwOjo6OfQBP/JX9y+YvD5i/5/5f8par+kp+Tj2vDT48Y9F4C+R1n+OMn/nfsSf8X9rn/1fInacWHu9HfYCr9k7TlTyL/m+bXT1fjP12Fj8jP7g1nZmYCAgJcXV3d3d2dnZ09PDzc3d1tbGwEBQUdHBwOnzVWV1c9PT3BP/YPlIaGhsePH0dFRf37KEMg2uTxCb5+TrBYbHFxsbe393Eg7n9maW9vj4mJ+f2WLxwO19LSkp6efkwGgcOytbVVU1OTnp6O2oLhThyN9nWcQsCHAWKH/Tsm3t7eXldXF8Q1hG8gntefc5IjCLK7uzs/Pw+n+/9UJeFaeXp6Ghxvf0N2HA63urq6sLAAN+xLS0ubm5sbGxtDQ0O/kz4K5Ge1YUNDg4qKCrgHnzt37s2bN69fv37y5AmAEw+nXFpaEhYWrqioOOYjh4aGcnNzf9F2MzY2du3aNQi4/m8SHA5nbGxMRER0fP/Mj8ru7q6trS0RERH6Sg4ODjo6Og4Hq/2vkIyMjB9++OEIPc+vkuXl5dnZWRwOZ2VlRUREhDo6HF/W19dVVFTo6elRXBqCIDk5Offv3//FuzIcDjcyMgKm5+joaCkpqV97vXZMqa+vp6Wl5eHhQbXh2NiYhobGz4VD2d7eXlxc/MV1HY/Hg1fKceoAXkrHrHBpaSkpKenhK+//fQFkNEAef0N2AoHg4+PDzMzMx8fHzc3NysrKz88vKCioqqp648YNFPf1e+RnT8oLCwvg8t7W1kZLSwueBO/fv3dwcJCVle3s7KytrQXXsIWFhaGhIVTfw5qJ8jLBl5ubm2NjY+DH5Ofnd+fOHfgeQmVCysNjBfz75OTk3N3dweNpc3Nzb28Pi8XOz88fCToxNzd3hBHr06v04f0ChBhG1dbq6urPAZbBHQ85dNVz+BEZGRlsbGwoEgiLxZKTkx/2uf+E/NyMPcIi8ZuXdHR2fVjCh/OTlJTUxcXlw4eiPkyffpaPjw/Ej8/Jyfn6668PnxiOX/+srCwuLq7DlELT09NZWVkfUh8eKbOrq4uYmBhcwTo6OrKyso5/sDhO9Q6ncXd3f/jwIVo+kCf93A4lNTUVEMSfLn90dPThw4fgAPuLFfD19dXR0UE/frqlu7u7t27dkpGR+cViP/3lb0hzWLq6uq5cufKJOIifKBCHw9na2mZmZu7u7rKxsTk5Oe3u7oaGhmZmZjIwMAA30u+Uj2vDwz3b3NxMT0+PQlMdHBzIyMi0tLR4eHi0tbXX19efPn3KxMQEEJ+QkBBtbW1LS0tFRUV0ZJSXl3t7e3t6epqamgI7y6VLl8zMzMzNzTU0NN6/f9/T06OrqwvsAAQCobCw0NLS0sTEhISE5MWLF+/fv5eWljY2Np6YmMjMzOTi4kLhRMvLy1FRUTo6Oo8ePWpsbMzLyzMzM7O3txcTE1NTU8vKylJTU5OSksrOziYQCJmZmUpKSl5eXvfv34do9AiCvHnzBmh19vf3g4KCjIyMtLW1ExISdnd3X716ZWxsXF1dvby87OTkpK+vv7Ozk5aWpqOjo66uDrG7xsbGPD09fX19+fj4GBgY0AlcXV399ddfS0pK5ubmenp6Ghsb5+fn7+zshIeH7+zstLW1mZubBwcHr6yshIWF6enp6erqohxQCIKggFbAOzY1NRkbGzs4ONjY2EhISAB4Ji0tTU9PT0dHJz4+/v79+5qamh0dHe3t7Y6Ojm5ubqampuA5HxUVZWxsrKurC1js8fFxDAajo6Pj4eEB69Dc3Jy3t7eZmZmZmdn4+Pjt27eNjY0tLS0tLCyAtnJ4eNjPz8/c3BzQ4oODg/A2g4KCjnARbm9vP3z4kJqaOisrKzs7m4iI6OnTpzo6Os7OzuABOzs7GxIS4urqCqhKVDIzM/38/FxcXAB7np+fLyQkFBISoqenFxcXh8PhMjMzi4qK9vf3p6amnj596ubmlpSUBKN0fHzc3t5eW1s7MTExOzv773//e1BQ0NDQ0Js3b1JTU5ubm4FQa2RkpLKy0srKCjYmwcHB2traISEhqIbd398vLi62tLT09vaen58fHBx8+fJlUVFRTk6Og4NDZWUlPG5zczMqKsre3l5ERERdXR21bFZWVubk5ExOTpaXl6elpTU1NTk4OAQHB8NS5OXl9cUXX1RWVu7t7Y2OjmIwGHt7+9HR0c3NzfT09OTk5IKCgpqamqqqqqtXr+bl5YHjsaurq6mpaXt7+9LSUnBwMBA9rK+vp6enLywsyMjIUFJS9vT01NTUgH5ZXFxMS0sDL+6tra20tLSgoCA4tBEIBG5ubgUFBeRfGmd+fj4mJubly5ejo6MEAqGlpSUrK6uzszM2NjYyMnJycpJAIBQXFxcXF4+Pj0dERGRmZu7s7GxubpaXl5eUlBQXF4PWbmxsDA4OTklJgR0JHo8vLCwMDg4GBgNUh4SFheXn57e2tjIwMOTk5CQlJWVkZKBQ19jYWCcnJ3j7QNsBzDSHnfPxePzExAR4tgsLCwPmem5ubnBwkJ2dPTU19dWrV7GxsajzeVFRkZmZWXZ29kdV3Efll++UU1JSaGlpUdXm5+dHQUHR2dlZUFBARkbW2NjY2tr6P//zP9HR0YuLi+fOncNgMGNjYw4ODsCMAFU3MDDo6ekJDAysr6/n4OC4detWVlZWbGzs6dOnCwsLZ2dnWVlZKSkpEQQJDw+XkpKqrKysrq6+efPms2fP1tfXeXl579y5A73GwcEBEE4CgWBubi4tLV1dXa2np8fFxZWZmfnZZ58pKCgAEzUjI2N2dvbjx4+pqan39vbKyspOnjz54MGDrKwsRUXF8+fPLy8vJyQk/PDDD0NDQ6GhoVJSUvX19Xl5eZcvX05NTY2Jifn8889TU1N3dnbu3Lnj4OAQFRUlLi5eVlbm6enJwMDQ1tamrKzs7e1dUVGhrq5+7949FITw+vVr6IqWlhYHB4d//OMfZWVlb9++PXnyZG5u7tDQEDs7++vXr4OCgpSUlOrr6729vW/cuIEGVq+pqfH09ExJSSEmJg4ICBgfHz916hQ5OXlWVpajo+OJEydg5ouJiX3//fdeXl4ZGRlMTEzc3NzT09MPHjz47LPPZGRkPD09Y2NjxcTEamtrnz17Rk5OXllZmZub6+joGBMTc+nSpYqKiqWlpUePHnl7e5eWluro6BQVFTEzMwPV0r1798TExKanpzU1NYODgzMzM2loaIqLi1VVVfX19auqqqysrIA+AJWZmRk6OjoaGprExETYGzo5OcXExJw9e9bf339rawt4uoqLixkZGQG+iiBIZGSkrKxsVVVVSEgIMzNzfX19WVnZlStXnjx5oqOjc/Xq1RcvXujo6NDT0/f396upqfn6+paWlnJxcUVFRQFHWXZ2to+Pj4iISHh4+IkTJ1xdXdva2gwNDWloaFpaWoSEhO7du7eyslJaWnrx4sXKykpzc3MXF5fc3Nw7d+4EBASAdhgaGsJgMLGxsUxMTI6Ojq2trYKCgteuXfP09FRWVqampm5vb9/a2tLR0fHy8srOzr5x44asrCza9oCAAFJS0tTU1JSUlB9//FFFRcXd3f3GjRs+Pj4LCwu8vLwnTpzAYDDp6enq6urJycnOzs73798vKytTUFA4efIkBweHurr6o0ePTp06paCgUFlZqa+vD5B8Dg6O5uZmIyOja9euNTc3BwYG+vj49PX1UVFRkZCQuLu76+np0dLS4vH47u5uCgoKNzc3AoHg7e1tbW1tY2NDQ0MDId4B0Q+1XVhYcHZ2hjrIy8vjcLiwsLCffvpJXFzc39+fk5Pz7t27U1NTGAzm9OnTOjo65ubmly5dcnd3r6qqYmBgICYm5uHhefr0aXx8vL6+fllZmbq6upqa2srKyvPnzy0tLa2srIDEBI/HBwcHGxoaOjs7S0pKBgcHMzExSUpKuru73759293dfWtrCxbX1NRUUVHRurq6gIAAHR2dzMxMIyOjn4tCISgoGBwcDP9jsdhz587x8/P7+fkxMzMDniIoKOjJkydA74aOtF+UX9aGPj4+tLS0KJsxoAURBAHG4IqKir29vVOnTsF1h42NDR0dnYCAgL+/P3qlgMFgyMnJBQUFAwMDNzY2REREgLd2a2uLnp4ezjWmpqZATyIkJAT0KgiCyMnJubq6IghSWFjIxsY2OjoaEhKCEkCurq7evn2bjo7u+fPnAM7v6uq6dOkS7IkMDQ0B6ldfX3/jxg04YjMyMsLIGB4eBvtFUlLSuXPnWltbAaMKJTMxMQH5jYSEhK+v7+TkJCj3O3fusLOzV1RU+Pj4yMvL+/n5CQsLg+0mJSUF6EOghMzMTHJyciDjmZ+fp6Ghqays9Pb2JiMjs7CwaGpq8vT0nJ+fl5SUBGjXxsbGxYsXnzx5AtkXFhYyMjJCQkLOnz8PI1hBQQEFrsrLyxsbG8/MzMTGxrKwsKDETeTk5AiCODg43L17d3d3d319nYODAxho9vf3ubi4rKysZmZmysrK4uLiKCkpCwsLX716RUpKCnyrCwsLExMTTExML168QBDExcWFlpY2Pz//6tWrYWFhWVlZFBQUL1++1NTUZGZm9vf3b25uPmL83draEhQUVFZWJhAIb968+fbbb8GOpqSkZG1t3d7efu7cOXt7+8zMTDY2NmNjY8jFzMysoaEB/3NycmppaZWXl9+9exfgySYmJioqKg0NDbdv3/b19T1z5oyjo2Nubq6EhAQGg9HU1ESZ1gYGBkDB9fT04PF4OEasra2VlpZSUFCMjIzATde7d+++/fZbV1fX0dFRZWVl4OBCEASHw3V0dNTV1UlISADTkpWVlZSU1M7Ozujo6D//+c+UlJSgoCARERFI7+joqKysjJ6ihoaGBAQEioqK9vb2rl27BkwcGhoa9PT0+/v70tLSbGxsi4uLMEGgqkxMTI2NjWFhYaysrNPT00tLS05OTlRUVD09Pc+fP798+XJjY2N7ezsVFRWwY6mrq1+6dElfX39/fx+Hw127du3x48erq6u5ubnU1NTr6+v7+/t8fHzAgtHe3l5UVBQeHn7mzBlwm+fk5AT1DdfKw8PDlZWV9vb2165dm52dBTaT4uLig4ODwcHB8+fPx8TEAKlXW1vb7u6uk5MTHx/f5OSkpKSktrb27OxsaWnp7du3YbT09PScOXMmOjp6YmKirq4uOTn54sWL0dHR9fX1169fhwg2ZWVl6enpdHR0QJDh7u5+//79rKwsEhKSrKysgYEBKioqGxsbQ0NDVlbWurq62tranzOMHtaGy8vLZGRk8fHxBwcHL1684OLimpiYuHHjRmho6MjICGiGYxpMflkbBgcH09HRoWdAPT29Bw8eIAgC+OqmpiYCgfDTTz9BCzs7O/v6+vz9/c+dO4eq5N7e3pKSEmtr6xMnTuTm5kpKSsrJySEIMj8/T0tLCyTABgYGwMbKx8eH0kmJiYk9ffoUQZDd3V0+Pj4FBQUTExOUKnljY+P27dvS0tItLS2jo6MIgqysrKDvXk9PD8qpq6tjZGTc29sbHx9nYGAA0oH3799TU1MPDQ2lpaWdO3euvb2dhYXFzs4OQRA8Hg8wewRBXr16xcvLa2dnFxkZube3d/v2bSkpqf7+fqhzQkICLS0toFlev34NlCpQt7S0NFJSUki2v7//6NEjOjo6Ly+v1NRUgKxXVFTs7+8zMzODbXFzc5ORkRFU/97enomJiZiYWGdnJx8fH6wcDg4OcLRHEEReXj4wMHBiYiIqKur27dtw1ktLSwMCRGtra11dXbTMZ8+eIQhCIBDk5OSMjIwMDAxgN8rKylpWVhYaGnr69GmUrROPx9+6dQtIiYHGHN0pd3d3t7W1LS4uVlVV+fj4CAkJkZCQwOl+a2sLPK52d3dFRUWBU/LNmzf//Oc/oQfU1dWdnJwaGhqIiYm9vLwSExPb29uh3xAEoaGhQe1fGhoaqqqqGRkZnJycMOSsrKwMDAz6+/u5ubnt7e3JyMg8PT2jo6NbWlomJyf5+PjQtRPeCD09PVhvCwoK+Pn5Z2dngSLT1dXVyspqaWkpLy/vu+++c3FxCQwMzMvLGx8fB5NoRUWFqKhoUFCQsbExLMy2trbQlsXFRXp6+oyMjIcPHwL3DIIgrq6uKioqqJ1rYmJCSkqqsbFxZGSEmpoabO66uro3b95EEERVVfXevXt4PF5VVZWKiiokJCQoKAjIq58/fy4uLg6FBAQE3Lx5c3193cnJiYiIKCIiIjg4ODIyEo5ZUVFRX3zxBUr5Q0NDY2FhgSBIVVUVIyMj2LulpaWfPXuGxWJdXFz09fX9/f2pqaljYmIQBOHn53/8+DHkXVhYwGAwZmZmenp6DAwMKysr1dXVjIyMcDLF4/GUlJQJCQlZWVni4uJw4omJiRETE1tdXQVzE2gAMjIyYO7a2dlhZWUNCQkpLy/X1dU1MzMjJiaOi4tLTU09efIkTDpQBWj4oMjISBkZmYCAgO+//97e3j4sLAzotUdGRrS0tCgpKTk4OA4zhB8W9KSMIMjS0hIDAwPsPEJCQgQEBKqrq0+ePGliYhIWFhYUFHQETvoJ+QVt2NzczMPD88033zx9+nR7e3tsbIyampqMjKy9vX18fJyZmdnAwMDPz+/zzz/X1dXNzs7m5ubOycmpra2lp6cH29DGxoampmZJSUlFRQUfH19NTY2amhpQBgGZsLa2tr+///nz52loaObn56Ojo4mJiV1dXX18fM6cOfPo0SN4zQEBAV999RWYzEAIBIKdnR0VFVVxcXF1dXVjY2NLS8vXX38NTM7i4uI3btzY2dmJi4s7c+ZMd3f3zMwMLS2tkZFRTU2NoaGhk5MTHo/39fX98ssve3t7nz17dvny5b6+PmAqBGbA8fFxIiKie/fugQsObO7y8vIAdl5bW3vp0qXHjx+npaXduXOHhIQEDbdSXFxMRERkb28Ph/rk5OS//e1vYMEhIyOD8EZ4PB7Mr1gsNj8/n52dHd798vLyjRs31NTUCgoKfvrpJzExMQRBnjx5oqKi8vbt26ioKCUlpaWlpbGxsVevXtHQ0CQkJMBRBZYBFRWVu3fvAnuCvr4+ExPT0tJSd3f37du3k5KSKCgo7Ozs0tLSzpw5k5SU1NvbS0xMbGlp2djY2N3dPTU1RUVFBeVgMBhSUtLOzs47d+4YGBi0t7e3tLSUlZVZWFhsbW3Nz89TUlKmpKREREQ4ODigvBhCQkI8PDz9/f1ZWVnffPMNWB5VVFQ0NTWnp6dJSUnt7e339vba2tpQS7SSktLdu3cPDg7GxsZYWVnLy8vj4+NPnz5dX1/f1tb28OHDlpaW4eHhW7dupaSkUFNTg37v6+tbWVnBYDAkJCTv3r1bW1sbGxsDYjHQMmlpaaysrHCmefr06XfffQd35YODg6SkpN7e3tDV6M21lpYWOTn59PS0tLS0pKQkgUB48uQJsN5OT08TExMnJiZGRUVduXKloKCgqanpzp07UlJS6Gjs7u4GtrHh4WEyMjI48WhqalJTUyMIoqioSEVFtbe3FxYWRkpKChbAtbW1nZ0dFxcXfn5+KMTX1/fq1atdXV3AQVdTU4MgCGz6urq6DAwMHBwcbty4ARxi5OTkcG6oqKigoqJaXl7u6OggJiaOiorq6en5xz/+UVJSMjY2dvbsWaDqEhUVhfUeQRAwc01MTLi4uFy7dm1+fn5+fp6VlRXI6BITEwUEBBYWFpKTkzk4OEZGRmBnCrZmKSkpZ2dnBEEWFxepqKhAIw8NDXFwcDx79oyOjq6wsLC/v//06dNRUVEVFRV/+9vfYDYhCPL+/XsKCgqYCKamplxcXMXFxcTExEAuicPhhoaG0tPTCQRCW1sbBQVFenp6Z2fnEX+Vg4ODu3fvonvDpaUlCgoK2Cv4+fmxs7MvLS0xMzPD7opAIBymRPm0/II2nJ2dhS1re3s7Dofb2NhobGysr6+fn58Hl6umpqaWlpb6+vrOzs6pqanIyMjnz5+/ePGiqKgIbtD29vYSExO1tLTMzMzq6upwONzAwIC5uXlERMTOzk5+fr6cnJyHh0dERISnpydYXqOjo+/fvx8XFxcfHx8UFAQnJqB6PUJHsbGx4e7urqioaGlp2dHRkZ+fr6Wl5eHhMTAw4OPjY2Zm1t7ePjw8LCsrGxISAjzPUlJSZmZmSUlJ29vby8vL2tragoKCGRkZ29vbjo6Ourq6GAzmcPg0ExMT1MsHi8V6eXk9fPjQyMiosLAQ4lhKS0tbWFiEhIQoKCigLNxbW1seHh4PHz6Eo2J/f7+9vT3sHNPS0oAWF8aTnZ2dgoKCgYEBSoqBw+ESExPl5eUjIyPt7Oy0tLSmpqbs7e3p6en19fWjoqKgEwYHB2NiYq5fv66mpmZubg7btObmZjk5OUlJSRh/Kysr1tbWkpKSRkZGJSUlQIkmKysbHh5uampqZ2e3traWl5cnKysLyjQyMlJcXNzY2HhoaKi8vFxCQiIpKam2tlZBQUFdXd3Nza29vd3S0vLevXsKCgqpqangBQX0nAiC4PH4tLQ0GRmZ+Pj44OBgERGR58+fb29vv3r16sGDB2Br5uXl1dDQcHR0RG9OZ2ZmNDU1BQUFoUwEQUpKSvj5+Tk4OAwNDWGT1d7eTkdHNzExkZWVxcHBISQkZGBgMDY2hsViNTU1geswOjp6dnZWTEyMl5e3trbWzMyMnZ09Pz8f+urOnTsw1REESU1N5eLiunfvnrS0NFjuEQR58+YNJSUlkJzfvn3b09NTSEiIn5+/oKBgfX2dlJRUXFx8ZGTE3NycgoLCysrK0tKSmpo6ISEBppyDg8MPP/xgbm7+9OnTixcvWltbA5HaxYsXMzIy6urqSElJbWxsNjY2tLS0gGXaycmpoKCAlZWVhIQEqDDhQkBRUXFmZsbNzY2CgkJQUFBPT6+lpUVMTKygoABBEAsLC1ZW1oGBgYiICBISkqSkpI2NDU5OTl5eXmVlZRISEklJyerqanFx8Vu3bjk4OLCwsKipqaWmppKTkwsJCYH27+vrY2FhAR4tcnLy/Px84M1lZGQUERExNzcHXoLU1NQzZ87cuXNHQkICgg6lpKRQUlIKCws3NTXh8fg3b97w8/Pr6+urqBd8fo8AACAASURBVKjAFOPj47tz546amhoZGZm6uvri4iIGg6GjowPLUkxMDAQ5QBDExcUFHg06VFlZ2cDAoLa29sGDB+rq6qampra2tmtra5aWluiWFkGQg4MDIANmZ2cHO7u/vz8REZG+vv76+vrLly8vX76cl5f39u1bKioqQUFBYWHhvLy8Y959//HIvP39/Q89IdbW1g7THB0cHKBoFqCfQvPCP6hTCOrPlZWVhYaSOCKoWwzwR6EEXCgXFrBLTUxMQHwo1IcGh8Otr68fZk9aWlo67EG9u7traWl5xLEcCKPQj1tbW1BbMNWh/Q6+poCGPjg4OIykPrxS4XC4qampIw5JCIJAXigfj8erqKi4ubkd7sPR0dH4+Hh2dvbp6Wn0Hm1ra2t9fR1cUtFngU0K/bi2tgY+Ruvr6+gjlpaWsFjs+vo6/AXTGEoPtbOzs7y8jP4/OTkJHldJSUmampro0wn/4geDjNvb2+vr69D2tbU1WB3X1tZmZmaAfAltLNjm0KUOfK2np6dR36PExMQ7d+7A8FhdXR0fH19aWoLKw0XzxMQEVAOLxYJ3LjCGAXkX4V88cmiEubW1tdHR0SNxt1dWVubm5lB+MBgMGxsbBAIBfgJ4+/T0NDBNLSwsrK6uQpnLy8tLS0uQEfLi8fjd3d3FxUV4ucvLy9DA/f396enpsbGx5eVlLBY7Nzc3Pz8P5SAIsr6+Dg8iEAgzMzNjY2PAVAZfQvaZmRkY2PPz81D42tra+Pg48I/Nz88Dc93U1BRMDajD/Pz84uIiOJ/BMJicnIRXD5xa1NTUbW1t4+Pj6AtNSEjg5eVtbW0FNlZ40Pz8/MLCAhoye2JiIi8vD2y1CIJsbGxMTk4uLCysra2h2PbJycm6urqFhQWozNLSEoFAAPA7zJ3Z2dnJyUmISL6+vl5XV1dfXw+DEN7j4QkInTw7OwtTY2lpCcoEyjt4NCQbGxubmJg4fsjiP1Ib/lqvpWOmHx4e9vDwePDgAewmfjPoqrGx8eLFiyjv/Kfz7u/vZ2dnGxkZgd/PR7Mcs/6/FrD4Yfrt7e0rV66g5zJIUFlZaWRkBOedYz76DwchNDc3H1bQv7b8Y3bgzs6OhYUFGuLmF0v4RJr/OMrz106H46T5Q7q9vr6ejIwM9WoASUlJERER+Tl/1eMM9Z+r229AWP6eco4p/wWsDS0tLXJyckDv/pvl4OCgqKhIT0/v+fPnx+nBra0td3d3Ozu7w/Gd/1PS0dFhaGjo6uqKGrng0tbKysrIyAgYuf8Py8DAgIuLCxqK6C/5w2V7exuDwRATE6MX9AiCzMzM6OjoMDExHZ87+r9d/uzaEHb1v5aw66OFbG1t7ezsHBP2BEBX9P/f8/TfL3DqBEGrBNTNQIz8H6/hv1Xg8P6frsX/ZcHhcACC6OnpOWyrgW9GRkb+bw8wVP7s2vAv+Uv+kr/kf0d+WRsODAz817EP/B75MyyDf4Y6HFN+W1X/ixr4G+R3tu6/q3P+KAvgn0F+QRtmZGQICQmhDp//V2ViYsLNzc3V1RW9e/2PSHt7u7W1NYRAPCKdnZ3W1ta2trY/RyrxHxEY4isrK05OTuANi8Ph2traampqKisrwSX+52RsbCwoKOjVq1dHwM6/WRYWFt6/f/+fmnW7u7vA8/Q72eFAIJwWRPj6/aX9UYLH47Oyso7ctCAIsrOzU1NT093djTqKHBG4aALvgn8fQd/vl09pw5WVFU5OzqKioj9qvB5Tfu3d6JFLveNf26EZcTichoYGBQXFYT6+zs7O9PT0n2Me+223k5++31xaWqKhoQHgIwgOhyspKent7V1dXeXh4eHk5EQHE+Ff8tHCl5eXa2pqjqk6P6zJz91dfvg9Doezs7N7+PBhUVERJHj79i0lJaW0tPSR4NRHStja2pKVlUVDxR5J89E39YneIxAIT548efTo0RHvLsIh+TDjh/9/+kEf/QcdQvr6+hcuXAB2uCMpcTjc5OTkh8HOf+4Nbm5u8vHxgV8q4V/EEB/2ycrKCjiEfaIhH7brox3y0fIPl7y/v+/j46Oqqgr3mQQC4eDgYGlpaWdn5/379wCjQLN8mJ1AIFhbW5uZmR0pHH0cOBsdqeRH3+NH39HhZBBY+TesJZ/ShnV1dUxMTFlZWeD2VVFRkZWVlZeXBzcSb9++bW1tbW5ubm1tHRgYaGhoaG5uLiwshKVjbW2toaHh8Ovv6ekpLy8H16GNjY2ZmZmdnZ2JiQmo9M7OzsDAwMi/wv2BDpqenh4eHgbQwvz8fGtrKzrWsVhsdXV1b28vZCccuidB/hWEE1zJdnZ2Ghoa+vv74Spmd3e3paXlcAhHiDoI7s2HQ6BpamoyMDCgH8fHxxsaGo741iEIAushes/T0dEBOCQISrmysrKzs7O+vo4GllxeXm5vbz+sZBcWFtDshoaGampq6E9LS0tXrlwBKCjqhop6RKJ16O3tPbIlef36NRMTE1ywQHx0YEVbWVnB4XAHBwcQTOZIUaurq4f928Fv7sjEJhAI09PT6GVUf3+/jIzM4VXk4OCAhIQE4pGjctj/Ee234OBgISEhtCvAVw75/8qRjOAfh1YGXOghwdTU1GGTzicINI+06LDL4c8JOEge/mZnZ+dIxpycHCIiosPeqWgdJiYmGBgYAHEBcmQN+PByLycn5zDD44eCw+GkpKSsrKx+sfJ/iJSUlIiLix/2xu3t7b116xbMdx0dHRRsDvKhbi0pKTmMazginp6e9+7d+0OqGh0dTUND8xuoLT+lDUNDQy9evAhkWeHh4crKyl5eXlxcXA4ODt3d3QICAiQkJNTU1KKioi4uLidPnhQREVFSUmJhYbG0tHRzc5OQkODn5weak9evX7u5uTk7O2tqag4NDfn7+9+5c0dYWPjOnTvgObG5uamoqMjDw1NfX7+7u2ttbQ1OmLy8vM+fP8/LyzM0NARMBcQFtrW1NTMzExAQQEGInZ2dioqKL1++BPC2rKxsW1vb7Oysn58f4HNra2tXVlZsbW1tbGxUVVUBvFFWVubu7h4QEEBNTc3IyIiCZ4eHhxkYGIiIiKytrQcGBrKzsy0tLfX09LS0tAA/RyAQtra24uPjHz58qK6uLiEh0djYGBcXh8FglJWVY2JimpqaANiwsLCQl5cHEcebmpo8PDwcHR0dHR2XlpZGR0etrKzU1dWNjY1hnDk4OGhpaaGvID8//6uvvrp9+3ZKSoq9vT0bG5u3t7eCgoK9vT3o/eXlZU9Pz6dPn5qYmKCwCjweLy8v/8MPP2hpaQUFBcnJyXl6es7OzgYHB2toaFRWVtrZ2enp6bm4uMjJySkrKwOgMC0tzcfHx8/PD3ARr1+/9vX1NTMzQz00kX8RXIaEhBgZGaWnpyMIEhkZef36dV1dXYCRQc9QUlLa29sPDg46OjqamZk5ODgoKys7OzvDnXh/f7+Xl5eNjQ0bG5uMjAxomfT0dH9/fzc3t6ioqPHx8ZCQEF1dXR8fHyUlJRsbG9DRVVVVdnZ2lpaWcCpvbW11dXXFYDAeHh6tra0YDMbHx2d7e3tgYMDb2xtgRTMzMyEhIb6+vr6+vnJychYWFgMDA+hExePxGRkZ2trampqasEY6ODgASYySkhLAexEESU1NBTYB2Bbt7e3FxcU9fvz40aNHU1NT+/v7L1++DAwMlJWVpaGhAa/Y6upqV1dXIyMjKKSuro6IiAilg33x4oWurq63tze4yvv6+lpaWrq4uKBuxkCKVVdXV1VV5eHhERQUhMFg7OzsAOkIMjMzQ0lJeffu3YqKiu3t7ZSUFA8PD2Ch7+rqCgsLCw8Pd3JyioyMLC4ufvbsmbe3t6WlZU1NTVFRkYWFRUpKCgQEB/p3Dw+Pw4UjCJKcnOzn5+fu7g763c/Pj4aG5vXr12glgTIKg8EMDg4CijExMRFCvEOCqqoqd3d3T0/P4eHh/f39mJiYoqKiiYmJpKSkuLi4ly9fxsTEwIqyvr4uKChIRESUmZkJE9/MzMzJyWlsbAyHw8XGxoaEhHh5eb148eLg4CArKysgIMDPzy86Ojo/P39vb6+7u9vJycnKygqQSwYGBl988UVwcDA6nY8pn9KG6enpfHx8IyMjXV1ddHR0QBBfXFz8zTffVFdXOzo6srKyVlZWtrW1ZWVlffbZZ9HR0Wtra+rq6qdPny4pKeno6Lh8+XJgYGBfXx8NDU1HR8fy8vK1a9fc3d0TExO/++47CwuL8PBwFK8aGhp66dKl2dlZ6OWUlJTZ2VkBAQFQRm/evMnPz6ehoSkpKYmKigK+oMOhTSHx48eP8Xh8XFzcd999V15eHhYWxsLC0tfXV1tb29TUZGlpqaamNjIy8vjxY2Fh4ZqaGhERkZSUlKGhIWVlZQYGBnRvODs7y8XFRUZGFhcXV1RUJCoqWlRUNDMzo6Wlxc/PD8vO7u5ucXHxF198ISoq6uPjY2Fhwc/PPzg4CGjWjo4OISEhRkZGHA5XUFAgKCjY3Nx89+5db2/vkZERVlZWKyur3t7ekJCQzMxMKioqQPXZ29sf1oaVlZU0NDTm5uY1NTWOjo5kZGQ5OTkpKSmXLl0CSjvgNBsaGlJVVWVjY0NR93p6ehcvXvT29q6trSUmJlZTU8PhcNbW1qampmNjY1JSUpcuXYIuvXnzpry8fHZ2NhsbW3l5eWFh4dWrV2NjY5mZmTMzM1NSUlA2yf39fXl5eRMTk9HR0fDw8CtXrjQ2NiYkJFy+fNnf3x8F2APmH4PBTE9Pi4iInD59Ojk52d/f/8SJEw0NDYODg3Jyci9evCgpKRETEwMGkPT0dEFBwY6Ojvr6+qtXr3p7e4eEhHz55ZdOTk45OTmUlJSxsbE9PT18fHxxcXE5OTlXr14tKSlRVlY2MTFpaGhwcXFpaGgQEhJiZ2ff29vLyMgIDQ198eLFjz/++ObNGzc3t88++8zc3Dw6OpqKigrF6iIIMj8/HxoaCuNcVlZ2aWnp/v3733zzja+vr5eX1/nz54E0U1ZWtrKy0trampycvLu7297e3tbWNicnR09PLzU11dzc3MLCIicn58GDB0RERGNjYy0tLYKCgrm5uVlZWZSUlFDnkydPiomJNTY2RkREaGtrv3nzho+Pz8rKCoPByMnJVVRUaGlpAaodQZC3b9+Sk5M7OzsD/Pn27duxsbEiIiIcHBzo6aS/v5+UlJSBgSE9Pd3X11dWVrawsFBDQ0NCQqK1tZWenv7LL78UFRW1traGHvD09DQyMrpw4YK9vb2Dg8PVq1ffvn3b1tbGwsJSWFhoaGj46tUrtGdCQ0Pl5eWzsrIsLS15eHh6eno8PDxISEjc3NzQ04ODg8Pf//53dXX1jo4OGJwBAQHKysrMzMyDg4Pl5eWSkpJpaWkYDEZYWHhoaIibm5uPjw/oSj///HPAd4JuHRsbo6Wl/f7778PDwysrK21tbaOiou7evaupqbm9va2iovLZZ58JCwvr6+sDNVFOTo6FhcVPP/3k7+9fUFAgLCycnJzs6enJzs5eVFTEwcFBRkbm4eHxa68BPqUNAfe+vb3d2NhIR0cHu7yWlpYTJ06UlJQ8ffpUVVUVUpaXl3/33XeAMra0tOTi4iIQCDgc7tatW8+ePQsJCfnmm28kJCQkJCQ0NTXLysrevXvHxcUFVnbUBACg/ZSUFBcXlwcPHsDuA7DZ5eXlTk5OxsbGN2/ezMnJGRwc5ODgYGJiMjIygq0llGBtbQ1Q7a6uLlpa2uHh4draWhYWFnp6ejMzs4qKCkZGRlFR0YCAAHl5eU1NTQcHB0FBQWhCUFDQkZOyuro6JycnjAwyMjLo2YKCApSMAGY+IyMjML+qqamRkpL6+/sbGhrS09MPDAyUlZVRU1O3trb6+/sXFRUVFxefPHlSRUXF39+fl5cXg8HMzc3FxcUB4Qcg4Y/sDQcGBlAWMisrKyUlJQRBcDgcHx8fHJ+B6gPQx6KioujZDZoDZ/PQ0FA+Pj4sFquiogLdFRwcbG1tDSlDQkJISEi0tLSAYMbJyYmHhycmJkZeXp6ent7ExAQ9+rW0tHz77belpaUIgqyvr9+8edPT07OyspKLi+sI7pCSkhLA/D4+PkB8MDU1RUtL29DQ8OLFi3v37sH7evHihbi4OBaL5eLiUlZWhuyGhoa8vLylpaVsbGwwVSQlJSHK9tmzZ62srKytran/H3vvHRZFljX+u7uzM+PMqDMGjBhGSYISVEAQQQQEiUoQBIkSJdPkHBqQqOSgJEGCgICSc46Sc845pyZ0d/3+OM/W0z8Mw4Tdd9/v6/nDp22qbt+qunXuueee8zmXLkVERFhaWl6+fFlfX7+0tHR7exuLxcL9GRoaSkpKAgzMmzdvSktLjxw5ArOmhoYGaYDx9vZ2Y2NjRkaGgICAiIgIkUh0d3e/f/8+/PXu3bsxMTFaWlq8vLwlJSVeXl6UlJQvX76Etx1BEDwen56eTkFBAePh9evXZGRk3d3d+vr6aCMYDIadnf39+/fU1NRv376dnJyEPtfW1qqoqNy+fVteXp6ent7R0bGkpIR0da+iogLqCZZHCILU1tZSU1OjQ3RxcZGenl5HR4dAIAA0sLy83NHRkYWFpaWlhZ+fX1FREeAdERERLCwsRCKxsbGRgoKiubl5eXmZiYnp3bt3DQ0NQJl7+/YtakltbW0B3QNuERcXV0BAQGxsrJCQEGlJk/T0dLA5iEQiBoORlpYGIOu+ffvev3+voqJCTU2dnJzs6+tLTU09MTEREhKirq5OIBCwWCwdHV1HRwckicKvqKioCAkJEQiE9fX12tra5uZmOTk5amrqzc3NxMTEa9euQYairq7ujRs3EATJyMi4cePGysqKhYXFqVOnCgoKXr58SUdHl5CQICkpiYLafpd8iX2dnJy8d+/e2dnZsbGxY8eOweuXkZFBQ0PT29vr7OyMerhKSkq++eYbWHtaWFiwsrLicDgcDge41oSEBBglaPtVVVX8/PyoVQiCx+NVVFTIyckzMjKKiopoaWklJSVnZmYmJyevXLny9u3bubk5dnb2tLS0wcHBiYmJjIwMRkZGWVlZ9FXU09MDd1VhYeGvv/7a1tYGvqSkpCRKSkpNTc27d++S+lm8vb0pKSnB42ZsbHzlyhVSr5mcnBwnJyeCIDExMZSUlODSgtGPEoq2t7dZWFjAapaXl0dhJOhfJSQkZGRkjIyMiERiVlYWGRkZWsCBSCRqamoaGBgQiURxcXFnZ2cEQaytrUnx7mVlZXv37gXcgIWFBUD2x8bGzp8/D2BEOjo60uNRcXd3Z2RkhEsbHR3l4+OTl5f38vKCIQKLRzjS3NxcUVHRxMSEiYkJ9Qqtra21tLRERkYC4RnctR8+fNi/fz/wvtbW1q5evfrs2bPy8nI6OrodBPyLFy+CtnVzcwPl3tvbe/ny5ffv3zs5OdHT04PW9vDwkJCQwOFw3Nzc6FjCYDB37twpKChgZ2eHlfW9e/eAtXfo0KHU1FQAwCAI0tXVFR4eDuDeurq6p0+fKisrIwiipKSkrq7e2NjIxsb2+vVr4AOBSaWmpgZqGiQjI4ODgwNAsyIiIgQCwcHBAeb4+fl5ZmbmhIQEBQUFLi6uDx8+1NbW9vf3JyQkHDt2DK33kpSU9NNPP/X39yMIAn/q6OgQExMDZh2CIFgs9ubNm3l5ebS0tEVFRV1dXadOnXJ2dq6vr6+trYXx+fz5c2Fh4fPnz6MJV0ARhzeOh4cHfBc1NTUMDAzoEAU8KAaDQRCElpZWVla2oaGhsrKyo6NjZWWFn58f3bKIiIiAq6uoqKCiouro6BgbG+Pl5S0qKlpbWwsLC1NQUKCgoHB0dIQXf2Nj4+TJk2hBCGVlZXd396SkJDExMdJ9ufLy8gMHDsDi1MDAAFgMw8PDv/zyy7t376SlpZmYmLy9vcPCwsC3aGVlBcaKk5MTcOpIxdDQEMZMc3Pz/fv3U1NT9fX1KSgotre3379/z8PDA0O3vr7+zp07pqamDg4OMBS1tbWvX79eX19fUVHR2tq6trYmISEBczDIDhftF+SztiHg7ykpKf38/BYXF0NDQ9nY2IyNjTU1NRMSEjo7Ox88eMDGxpaRkbG1teXj43PmzBlzc/POzs6bN2/+7W9/Cw0NXVhYoKGh4eHhGRsbExcXv379uo+Pj6OjY11dHRaLPXjwoIuLyw5Xt7u7+8GDBycnJ9fX12loaKCoTUdHByUl5YMHDwwNDX/66afnz5+D07CyslJQUNDV1RWdrIyNjamoqJydnUVERPbs2RMSEuLo6Kiurt7U1CQkJOTj4/PixYvz58/7+PgEBQUlJCRUVVX9+uuvEhISzs7OVFRUx48fJy0Xp6Ki8ssvv8TGxk5NTXFycsJyVV5eHkq1IP/K9jty5Ahomfz8fHJychsbm1evXnl5eYFd9vz58x9++AFIJxMTE5ycnAICAtHR0Z6enuXl5QICApKSkn5+fkeOHNHS0gLYKmBBoQ9tbW3g/qusrBQXF+fg4BgfHx8dHf3b3/5mbm4+OztrY2MDC9XIyMjMzEz0VgQHBx88eNDLywvwAXp6et9++y36DgcGBjIwMAQFBfn6+srKyn748KG6uvr06dNmZmYZGRlxcXHx8fF2dnadnZ3u7u7q6uowEJeXl+/fvy8gINDc3Pzq1StwC8TExOzZswde14WFhYmJic7Ozp9//llJSWl2dlZRUZGFhWVubq6/vx9AzYWFhYcOHdLW1g4PD7927dqVK1cAW3vu3LnCwsL+/n5eXt6IiIj09PTjx4+DL5Kfn19BQaG6uhrgY8AxLS0t1dHRGRkZ6ejoYGdnr66u1tPTExISIhKJDAwMAJrbv39/WFhYcnLy/v37wb/8+PFjSUlJ1ILW19c/dOhQTk6OhIQEAwMDAFdu3bqFw+FmZ2f37t0bGhoKwNSMjIy2tra8vLyBgYELFy6Ii4t/+PChrq6uoKCAmppaXV09KytLUlLyp59+AibVpUuX2tvbV1dXpaWlsVhsa2vriRMnINFTVFT0/v37nZ2d1dXVtbW1VlZWMzMzGxsbV69eRXPgcDgcDQ0NYMdYWVl9fX0RBImMjCQjI0NtiJWVlUuXLklISCwtLRkZGTExMTU3N09OTjY3N+NwuDt37qBLN39//+PHj+NwuNra2m+//baqqgrQohAuA+5mExMTBQUF0IZ4PF5ERATM297eXsD/vHz5kpeXF12nIwhSVFT0j3/8Izw8fHl52dDQEBTQwMDAjz/+mJqa6uDgQEVFBdNkX18fDodTVFQUFhZGEMTZ2Rk+kIqGhoaQkNDExISjoyM/P399fb2oqCgFBcXW1lZsbCxAGBEEmZ2dffDggYqKSllZGbAkwDEFO7Q1NTU4HE5WVvbmzZs9PT3Dw8Nqamq7rwH5WW24urra1NTU2tpaW1sLyrW8vDwhIQHeqImJiaqqqpKSkubmZjwe39LS0t7eDgjPnJwcKICwvr5eU1NTUFCwvr4+PT0dFBTk4OAAHHzwA5aVle3YlWtubk5JSYEv8/LyYOm9sbHx/v17AwMDKI5RXFxcXl7u4eHh6+ubkJBAuhnX39/v5ubm7OyclZXl4eHx+vXr9PR0BweHiIiIuLg4oFy8fv3awsICGJB4PL6ystLS0jIwMDA9Pd3GxiYvL4+UZozFYmGAgl4A8jb8IuxiJycnm5ubBwcHw4wNUFsnJ6f4+HjQIAMDA97e3qj/or293dLSEovF+vn5DQ8PV1VVmZqavnnzJigoKCoqqrGx0d7e3snJCa3ht7W19fbtWywWW1JS8uzZM3t7+66urs3NTaj1UVdXNz09HRISYmZm5ufnR1qgbnx8HLzOMJknJyfr6uqidxuWqzY2NiEhIai/IjEx0dzc3M/PD7yxUNLE3d2dtGjRyMgIBoNRU1NzdnaG76OioqysrCIiIpaXl9fX16empjIzM62trX18fIqLiwMCAhwcHDo7O5eWlp4/fx4SEjI3N5eXlyciIuLh4REbG2tra9ve3o7H4z09PdXV1e3t7d+8ebO2tpaammppaQkE6devX9vb28OevpSUlJqaWlRUVHNzs5mZ2ZMnT0xNTbOysrq7u83Nze3t7QcGBuLi4oDbGhQUFBkZGRQUpKqqCoiz+Ph4Xl5etKJQfX29pKSkmZmZu7u7kJBQUVGRoaHh7du38/PzNzc3ZWVl9fX1BwYGHBwcJCUltbS0Xr16tba2VlZWJikpqaCgYGdnB8g7UVFRc3NzDw8Pfn7+sLCwra0tf39/CQkJRUVFZ2fnxcXFtbU1HR0daWnpzs7Ojo4OeXl5FRUVPT09GH56enrm5uahoaGoromJiQFu+YsXLwQFBTEYzNzcXHFxMSnzGY/Hv3jxgo+Pr6ioaGZmRkdHB9huqampsP8rLS2dl5c3MTGBwWA4OTnT09OTkpI4OTl9fX1HR0cVFRUdHR3z8vKUlZVFREQMDQ1Jd8O7urru3bsHJPOUlBQgawGiDT1menr63r17kpKShYWFT548ERMTa29vX1lZAXx9Z2enmpoaCwvLo0ePkpOTu7u7lZSU7t+/D4hMERGRd+/ekcYnFhUVCQgIREVF5ebmysjIGBoaGhoaSktLJyUlGRgYCAoKvnjxgkgkVldXX7x4UUlJSVdX99KlS35+fhsbG25ubtLS0kZGRlgsFiDbEhISL168CAkJoaWlJXV/fVn+o5l5H6cb/2ZA0OcO2N7e/s2MY9gy297e3oH0+VxEBYS8fvyLaGQJqckN7k7AUgFADL7H4/EfA83Q9uED6QHoPcHj8egeyMc9hIp9pCS07e1t1DPym0GtWCwWGK4g3t7eGhoa6A1Ez4XIG/i8sbExOTkJ/90RQTY+Pg63lEAg4HA42F6HPhP/xc6CAofQbfSuorUMV1ZW0Mgk9GJnZmbQCJvNzU3SE7e2tuCw5eVlgG4hCILD4UZHRyFYanNzc3l5GYfDQcfQcA1NhgAAIABJREFUfU/Icd7a2gJwHB6Pn56eJjVw0CToxcXFlZWVubk54F/BRU1PT0MI19TU1OTkJHrzl5eXSYFjKysraCOoXT84ONjb24s+a6Ciwf2EnkP00tra2ujo6NDQEOnAQ3li4+PjQKza3NwEMNr09PSOI2HCA9TY6Ojo5ubm4uIiYK/m5+eBKrawsDA/P7+0tDQ/Pw+tra6uzs7OAvirpaWFdMMBxsP8/HxLSwsYd1tbWzMzMzMzMxMTE6SDYWVlBfhs8OygmCVQv2AMdHd3d3V1QYo9XNTCwsLMzMz09DRpSVX4MDc3Nz8/TyAQ0E4uLCzMzs5OTk7C5SwvLz969MjLywvi1QwMDHh5eeGhTE5OjoyMwINDEGRpaWlkZERNTQ0cSruU360NvxADueOwHad8rp3d/Nzu+7b7pj7X8o5gtM+1/Ls69slGdnP6l3u4G8nNzdXQ0FBVVUXBX8vLy5ycnGfPngV79pMP4o891t97Q3Zz4h9u8082tZs7sPumdnkWqaL5XYf9hXfpN1vbZSf/wl9EZX5+XkpKysjIaHp6urGxUVlZGSUNf9zU2tpaZmbm50yTT8pXasP/y0IkEvPz8+3t7UlDyQYGBpycnLS1tdHtiK/yVf63SHNzM4DH7e3tIyIi0OSLHYf9MWX9VRv+nxNYZpIuUb/KV/lfJEQisa2tDV3a/4VW6ldt+FW+ylf5KgjyZW3473AQ/BkBh/3H3/+ZHv6bnC9EInH3rI7/njv8Xy7/Pk/Zn+nJHz7yf+oS/mvHG+ma94852T93+i7lL7YN7ezs0LDev1Dq6+sfP35MGlpIJBJfvXqlrKz87t27P9l4bW3tF1g1f0zgwVRVVSkrK/v6+pJGEqysrKSkpPT39xcUFCgpKUG2728KBCg4OzvvEkuzvLxsa2trYmLyMTflf69sbW3FxcW5ubmh0e//U0IkEru6uvz8/KAm38dSU1Pj5eVVX1//5UZ6enpIN7j/Y7K6uvrfUOLik5KWlvb27duPjYna2trAwEBI9P6cEAgEqLr1x37609oQlE58fPyNGzdIqRW/KaamplgsdjdH7nLjDGRlZQUNB0X/WlVVderUKdJEq923v76+7uPjAxG5Pj4+ysrKu6wQsJtfQb+EGrUMDAykoUX9/f38/Px5eXnDw8Pnzp2DCPPPCYFAiI+Pz8/Pn5+fFxYWZmRkRKNqPt4LJv28ubmpo6Pzz3/+E/IpSY8hEAhVVVXw/fr6emRkJLrd/OXr+l2yG8f2534FrWz38WHl5eUUFBRQPBcVHA5XXFwM8U9/YC94lxvoO97PlpYWWlpaISEh0i83NjZKS0vX1tZyc3NPnjwJ+UWf+4mJiYn79+/Hx8d/7ne3t7d3xL78Zrd3+eD8/f01NTW/vN9KJBIB+LRDX/87IgfQA169eqWoqBgQEIA6tTc3NyFGJy8vj5ycfId62fEKbGxsKCoqoiV/f698NjNva2vLy8vr2LFj6enp8/Pzi4uLBQUFvr6+kGQzMjKSl5fX0NBQXFycmpoKGfv9/f01NTUdHR1o/yoqKrKysj4HJpqcnPzw4QMENOFwOCiHODY21tjYSBrZNzAw0NraamhoqKSkRHrla2trXFxcaPpRV1dXZWUlqSm0tLRUV1eHBg93dXWhu6gDAwPU1NTu7u4EAmF6ehqNC1tbW6uurkZJEMvLyxCk1t7e/slBSSQSZ2ZmBgYGBgYGgAIJvKzu7u729va1tTVNTU1OTs7Z2dmOjg54wJubm2hr6urqKPmqv7+/qqpqRxbR3Nzc+fPnvby8EASxt7cXExObmZnp7OxEIxPhMqurqz9mUL5+/frQoUMQyL20tNTd3Q3XuLi4yMXF5erqiiBIZWXlL7/8gt6Wqakp9OZDtUwikTg3Nwe2LZFIXF1dhfKkMHnAzYEv4Rs0ZhCe1PLyclNT0/z8/I5RS7qHg04VCwsLbW1taOzkwsLCjtzN9fX12dnZK1euQEoWKnFxceTk5Og8Ac/0C7V0UFMdrWu6tbUFhU8h4nJ1dRVOh2qiO/qAPnphYeEdEKrExMRTp05tbm5ubm5eu3btkwArUuVSUlKy4+0gpfI1NDQcP34cLbSNkCDCPhmyCrK1tbVjofPxTD86OrqjLu4nJS0tjYqKakcR879WSPvW2trKzc0NSQTo3NPf38/Ozg6DipeX18XF5eNGSEsDtbe378gT3b18dqUMMM7vv/9eW1s7MzNTS0tLV1cXi8Xy8PAkJydXVFQcOXLkzJkzJiYmgoKC5OTkZWVlRUVFDAwM/Pz8CILMzMz4+PhYWVnx8PDIyMh8vBzo6OjQ0tKSl5fn5eUF1JWUlNS9e/ccHBygdjgsCWNjY83MzLS0tMjJyUlzDxEEmZ+f5+DggLTTrKwsExMTZ2dnOTk5SJceHh62tLSEHO+0tLQ3b95oaGjcvXvXy8tra2srPDx83759wsLC3t7ecGlbW1vDw8NGRkYWFhaQIjo+Pm5tbf348WMTExMZGRkRERHSZA9UCgsLeXl5+fn529vb6+rqIInKzs6OjY2tq6tLR0fn7NmzGAzm7t272tra8/PzycnJN2/ehAU+qg2zsrIwGAwGg9HQ0CBVAdnZ2T/++KOoqGhVVZW1tTUXF5elpSUbG5u+vj6M0b6+PgwGo6Ojo6mpuQNKHBUVdejQoZ6enq6uLgMDAwkJCTU1tfn5+crKypMnT4qIiOTm5np5eX3zzTdYLLa3t/fDhw/6+vpQ2Lu3tzc4OPjx48eqqqpiYmKQr4IgSFlZmaysrJmZ2dDQUFdXV1BQEA6HS09Pl5WVTUpKSklJwWAwSkpKEOnd3NyMxWLV1NRMTEzQN2ppaSkgIEBFRWVlZWVgYACDwUDCSUVFhaurq5KSEkz+ubm57u7uxsbGAQEBgK0MCwuzsbGRlpYmJyeHRwyysLBgaGj47bff6uvrt7e3Dw4Oent7e3p6amtr78iicXV1tbCwMDExsbGxWV1djY2NdXd3d3V1raqqamhouH//vqGh4fLycmJiori4+NDQUHt7u4eHh7W1dVBQEIFA6O7utrOzU1FR8fX1hQlDTEyMh4cH/Qk8Hu/k5PSPf/zDzMysrKzs9u3bXl5eDg4Ojx8/huyXjY2N4OBgfX19Dw8PSNqxtLSE2sG2trYeHh5GRkapqalog2/evPn73/9uYWEBCVRWVlbd3d25ubmamprFxcURERG2traBgYHi4uIWFhagtUtKShwcHJ48eQLp8N3d3TY2NkZGRn5+fqjeGRkZ8fX1fffuXUtLi5eXFyRoKioqBgcHk1bj2tjYcHJyOnHiRERExPr6elNTExaLNTU1LS0tHRsbCw0NheTx9+/f5+TkREZGhoaG2tvbZ2ZmlpWVOTg4PH/+HDAQQ0NDfn5+kLFKqsTX1tYSEhIwGIylpSXM2TExMadPn46IiEBZPnATDh8+jMViJyYm+Pj44H3U1taGUpHr6+vJycn6+vpGRkYdHR01NTXPnj2rqKjo7+93cXGxtbW1sbGJi4vbpT37pZWytrY2JSXl9PR0fHw8Kysr3ClPT88LFy6Mjo5KSUkBd2R7e5ubm/vu3bvb29vS0tJAhbGzs+Pg4MDj8ePj40FBQTvqQyMIMjAwUFRU1N7ezs7OrqCgMDY2JiUldenSpZaWlry8vJ9//jk7OzszM5OPj6+pqWlsbExJSenRo0ekVwXa0NLSsr29/fbt25A9rqenx8nJ2dTUJC8vHxYWNjMzo6enFx0d/fbt28bGRn9//4sXL25vbz979uz777+PiorKycnR0dEREBCYn59XVVVVUFDY2NjIzMw8fvx4XFycp6fnN998Y2Nj09DQcOvWLVLiA2QFIAiyvLwMKdtLS0tiYmIXLlyYnZ2Nj4/X0NDA4/FqamqHDx/OzMzMyso6ceJEcnJyfn7+/v37AU+irq5ubGw8ODjIxsZWXl4+NzdHTU1tZmaG/kpubi4NDY2trW19fb2trS01NXVaWlpqaur58+fj4uIQBFFWVjYwMJicnJSWlubk5CQNmomKijp8+HBnZ2djY2N4eHhRUdG5c+cyMjLS0tL++c9/Ojk5lZaW+vn57d2719/fv6am5t69e8HBwd3d3deuXbO2ti4uLj548KC0tLS7uzsKc52cnGRlZZWQkIDc559++mlxcfHNmzfAK4uJicnJyXF1dQXWpqSkpJ6e3sDAQGxsLDq+V1ZWNDU19+7dOz09PTIycunSJQsLi+npaU5OTi8vr46OjoCAgN7e3rt376anp5eXl589ezY5OdnLy0tNTQ04fefPny8sLEQH6tLSkoSEBCRl5+bm3r9/39fXt6WlRV5enomJCbW8xsfHpaWl9+zZ8+jRI1tbW29vbxERkYqKCl9fX1ZW1ra2NjY2Nm5ubgKBEBQUxMvLW1BQICEhkZKSkpWVdfTo0ezsbICDhYSE/Prrr5mZmQiCyMrKkjpq8Hi8kZHRmTNnPD09Kysrubm5paWlY2JipKSkIMHc09NTUVExNTVVUlJSQ0MjNTV137594F5kY2M7evSouLh4WFgY2iAWiz1w4EBoaGhaWtrVq1cpKCgWFxdjYmKoqal7e3utra2/+eYbDAbj6+t7+vRpHR2dvLw8Hh6eN2/ehISEXLx4MScnR0FBwcDAIDMzU1ZWlpRWx83NTUdHV19fr6iouH//fpgVjh49iiIdEQTB4XASEhI//viji4tLbm6uhIREeHi4m5vblStXysrKhISEvvvuOxkZGRsbm8DAwB9++EFVVdXT05OCgkJKSsrDw4OWlhaDwRAIBC0tLX19/aSkJHV1dcBbgDg6Oj5+/Pjdu3e6urosLCyjo6NpaWnXrl2zs7MjJbyYmZkdP37cysqqp6eHk5OTm5vb19dXQkKCnZ0dQRAXF5fHjx+np6cDAic7O5uMjExOTm54eJiRkfH7778XExPz8PD4XImCHfIlbWhubk5PT48gSEREBA8PD7SYm5vLyMhYU1MjLy//8uVLOB6DwXBzc29ubkJ24fb2NhsbG6DrPifLy8vPnz8HfNODBw8QBLGxsQFGy8zMzKFDhxITE+Xl5cXExOB4bW3tBw8e7NCGN2/edHJy8vLyunLlCijc4uLiQ4cOPX36lJmZGQxSoBaXlJTo6OhISUldvnwZQZC0tLRffvkFXpW4uDgpKanm5magMcLlCwgIGBgYvH///uLFi7Bw1tPTI9WGGxsbkIKGIEhycjITE1NRURE814iICDc3NzAHlJSU2NjYEARZXV1lYWEpKChAEISfnx/wJFpaWhYWFklJSQcOHJCQkBAXF3/48OGOVFCgV8GwePjwIYIgBAJBVFQU7C9aWlpWVlZhYWFhYeEnT56QPvXIyMiDBw92dXUtLS25uLgYGxtfuHAhNTW1pqbm559/Bju3sLDwwIEDo6OjtbW13333nY6Ojru7OxMTk5+fX29v78WLF4GbQOoyc3V1FRAQqK6utrCwYGZmjo6O9vHxgR6CUcDHx3f27FkcDufn50dPTy8uLh4QEEC63nz9+rWwsDDMJfr6+qampsvLywC2AoMuODj46NGjDg4Obm5u9PT0UVFRvLy8qK+QhYUF/Qz3393d/ejRowiCVFRUXL9+HXR3fX39gQMHUAIugiCvXr2ioaEZGBjY2tri4uJiY2PDYrEYDObq1at9fX3p6ens7Ozj4+NgN/n4+JCRkWGxWDs7O3p6+uDg4KmpqeTkZCcnJxoaGsheV1RUtLOzI+1JcHAweBJxOBwrKys85fz8fA4OjvLy8lOnTgkICLi7u9+9e1dKSmplZeXatWtgGtva2srIyECFW3SQBwcHHz9+HMzqlJQUYAUlJiYCzQF4CmDxeXl5Xb9+XUFBAciP7969Y2RktLe3B1rKs2fPPnz4sLGxgbYcHR0NXviEhATA1iEIcvHiRSDioKKnp3fx4kUwzAGICZQ/YErevXt3ZmZmbW1tbGyMlpYWwOOMjIygFpydnaWlpQFMxcjI6O/v39jYiL4ywPKBPaiZmRlKSsqwsLAPHz48evQITZGCPvj7+1+6dGl4eJhIJAJYBEGQnJyc69evT09PX79+XVNTs76+3tXVlYuLa2RkxMzMDOg7GhoarKysUGX3T9mGILq6umRkZENDQ6mpqadOnQIUhKurKw8Pz+joqKSkpLm5+eLiYn19/e3btyEfUEBAAG6ukJAQAwMDaV5nWVkZqUcJg8HAClpLS0tWVhYGBMCphoaGjhw5kpGRAcoFWmBlZZWUlCTt3tra2q1bt968eZOUlHT27FlwFuTk5FBRUcXGxlJQUACJD0GQDx8+sLGxtbW1wShBECQuLm7//v3wQsbFxcnIyAwNDTEyMqK4JxEREWdn58zMTFpaWpiptLS0YOgPDw/vcEwMDQ3x8PDcvn27q6vL3t6emZnZ3t4eVvqqqqo3b95EEGR6evratWtAKuTg4IBJWFFR0cbGJjMz89ixY7W1tbCOIM2V7u3tPX36dGJiIoIgVlZWKioqCIIsLi7eu3cPXkgGBgZLS8tPotxiY2PJycm7uroA0UogELi4uN6/f19eXv7jjz/C2A0ICNizZ8/8/HxDQ8PevXsB1AhSW1tLS0uLosVR6evro6WlBeImsGcMDQ1HR0fb2tro6elzcnKKi4sZGRkhDbaystLY2PjQoUPoxIkgSEhIyM2bN8HbJSMjY2Vltba21tzcnJGRoaamxsbGpqioeP78eVJsGh0dHew2TExMMDAwkK6UEQTx9vYG9lppaSkTExMsu8bHxxkZGUm1YVBQkIiICIxAWlpaYWHhyspKcAJAUQQODg4VFRUHBwccDmdoaEhOTp6SklJXV0ckEldWVsTFxcGHICAgAE9ETk5OW1ubtCfm5uYcHBwIgqyvr7Ozs4MNGxkZyczMXFdXR0ZGpqOjU15eDn72oaEhJiYmmCAtLCygzAOphIaGHjt2DN6axcVFDg4OExMTDAYDK9COjg5RUVE40sfHR05OztbWlp6evri4uLKycn5+fmtra3Jy0sfHh4eHh4aGBkVSwyMAHGFERASKobt48SLpugRBEGNjY3hf3N3dqampc3Nzy8rKoPP6+vqCgoJwGOBEwREJMEcEQTw9PZWVlbe2thoaGgwMDDg5Oa9fv47mRNXW1h44cAC04crKytWrVwMCAkpLSxkYGHY4UoODg+no6OBVvXDhgpOTE4IgaWlpPDw8vb29Fy5csLS0rK2thdECuygeHh4IgigpKcGo2L38Bu2VkpLS1NR0cHDQxsbm/v37zs7ORkZGcFsFBATOnz9vZGSkq6sbGxuLIEh5efmFCxcoKSkLCwuzsrIuX74sJiZmZmaWn58fHh5ORUVFWjbIwsKCiorKxcXl8uXLFy5cyM/Pv3XrFiUlZX9///T09J49e/T19fPy8mhoaBQUFKytramoqJiYmFDAMoIgOTk5P//8s6CgYF9fn5CQkJycXGRk5IMHD549ewYkpdOnTwcFBQEe5ujRowYGBurq6nv37s3MzKyqqtq3b5+GhkZRUZGmpuaZM2dqamoA4xwREREZGQnWopWV1TfffPPy5UsCgaCgoMDNzd3Z2SkpKUlKCQZ5+PAhOTk5giANDQ1///vfwVaan5+/ceMGGRlZS0vLzMwMDQ3No0ePXr16tWfPHgsLi+7u7mPHjsHGCDs7+40bN+Li4mxsbIBmCNLT03P69GkxMbGKior79++fPn26r69vc3OTi4vryZMndXV1NjY2VFRUISEhgYGBsHwD2dzc1NbW/uWXX3JycpiZmYWEhF6+fHn48GFbW9umpqYTJ07IysoWFhZCZ9TV1fPy8sTExAQFBRMSEl68eFFcXJyUlLR//343N7cdzIvNzc1ff/2VkZFxZWVlcHBw3759urq6CILk5ubu27fP3NxcU1PzxIkTBQUFVlZWr169qqmpYWFhIQ2EyszM3Ldvn6urq42NzbfffquhoVFWVqaiotLQ0JCfn3/16tXs7Gxubm4VFZXk5OTAwMCuri51dfXLly+/evVKTU3t22+/BZwJ2qCjo+OJEycSEhIaGxuZmZkNDAx6enqcnZ3l5eXhLUIQZGNjQ19f/9KlS6D+fH19z549GxsbW1FRgfqVnj59+u2330KIWFFR0f79+w0NDRsaGtLS0oqLi48cOaKhoREWFnb06FEXF5eZmRkgqpJORbq6ugcPHnz37l1TUxMQAxEESU1NZWBgKCkpkZeXv3HjRn19fUNDQ3Nzc1tb2/Hjxy0sLHA43P3790VEREjddgiChIeHf/PNN4Ccgcs8cOAAqAMEQfr6+mhoaGB6k5KSSktLy87OPn78+MuXL/v6+kpKSgYGBqytrWGmOXPmDDqxEYlEVVVVGhqaubm5Z8+eMTExwSUA9Je0A3p6evv378/IyIiPjz958mRcXNzg4GBNTQ14rmCaRxAkMDDw5MmTEPtCT08P2kBfX19MTGx8fNzPz29lZWVycvL69evodLu4uHj37l0FBQW41VxcXKOjoxkZGXv27AGHICoBAQEHDx6MiIiYnJw8efIkDLbU1FQaGpqurq7Hjx9fuXKlrq6upaUFOkZDQyMqKrq5uSkmJkZJSfm7qqP8Rrxhe3s7qs4LCgqioqLAx4/D4aSkpAwNDQFgCQc0NTVVVFTk5OTAKqyzszM0NDQgIKCqqkpQUHBHGdKxsbFXr14lJyfX1ta+fv26rq4uOTk5JiZmdHQUj8cnJSXl5OQsLy/X1tYGBQWlpKRUVVWlpaX19fWhr0FTU1NMTMy7d+9gP9rZ2dnMzCwtLQ18ZwsLCwEBAcbGxpGRkbOzs3FxcU5OTtnZ2YmJiZWVlXg8PjMz087OrrS0NCUlJSQkpLq6ent7+82bN1gs9sWLF+CALygoiIuLq66uJhAI0ENfX19BQcEde50IguTm5oIhsLW1FRMTAzPV4OBgdHR0aGgoEKIKCgqSk5PfvXsXERGRmJhYXl4eFRUVExMzNTXV09Pj5ORkZ2cXHBxMijOBKgKAVoyJiUEX4Pn5+bGxsSUlJSsrK9HR0bq6uk+fPiXdfJyfn3/+/DkWiy0qKqqqqjIwMIiIiIDyILCTo6GhUVVVtbi4GBgYaGRk1NbWNjIyYmVlZW5u7uPjU1VVFRoaqqGh4e/vv2O3GoJ+YP7f3t5OTU0FowCPxz979szU1DQhIcHOzi4+Pj4qKgqLxQYHB8fGxqL0GgRB1tfXQ0NDDQwMfHx8XF1dXV1d6+vrfXx8/Pz8goKCQKeXlJTo6+tbWFi4ubkNDQ1NTU1ZWlo6ODgAdiwsLIxUB42MjFhYWLi6ukIUgYGBgY6OjrOzM6mXanBw8OnTpxgMJjc3F4/H43A4Hx8fJSUlR0fH169fQ99GR0c9PDzQRX14eLi0tLSSkpK3t/fQ0BBQUX19fR0cHIKDg6uqqrBYrLOzM2nxjaamJllZWSsrq6KiIjMzMxcXl8XFxcHBQXNz84SEhP7+fnV1dVlZWXt7++bm5oKCAmVlZRh7dnZ2aFkP0uvS0tJSVVUFbTg4OHjz5k10a2hoaIiCgkJFRcXNzQ2MZTweHx4eDvt1L1++HB0dffTokaGhoYWFRWBgIOpTXllZefLkCcS6urq6SkpKQvmqx48fi4uLk+41l5aW8vLyampqgo157969J0+evHjxIisrS0ZGhpubOzk5GUEQOzu7a9euhYWFxcfH37x508TEZGpqysPDQ0hI6O3bt7DFYW9v/+rVK9JFa0tLi6qqqpKSkoGBQUFBAYFAsLCwkJCQ2FHIt6urS0xMzNDQMCUlRUlJydzcfHl5ubu7+9atW8HBwWNjYxoaGlJSUgYGBoWFhU1NTTo6OoaGhiUlJY6Ojvfu3QMrfpeyq+jrjyMh19bWODg4SOsB7jiGdOpubW01NzfffUDflxf5X/jrxxHUu/SeksrW1hZcyydD3uzt7WH7Yjd5EWjowyczgtEv0U6iO25fyGMhVSvoh48vHI1TgcbRBjc2Nr6cJINaghsbG9vb21tbW0AtQw/YZVYAeIhWV1fRcPEdJ5KirqB28PLyMmnMIJFI3DFmUGgY4Ll2/Ch6P1dXVwcGBnYE0wGMfWtra21tDT13YWEBdP3nIjeXl5eHhoZIHT5oawAx29jY2PFw19fXl5eXNzc34a/QDSigiCDI9vb24OAgvO1wvfAnCOv5mNK8tbWF7kBmZ2e7urqi11VRUcHJydnX17fDohwfH0cvf2Fhobu7Gw0JgOva3t6em5tbXFycnJycn58HYhjsR42Oju54XsDUgm9GR0f7+/vX19dXVlbGxsZGRkbGx8eJROLk5OTY2NjU1NTo6Ojo6OjIyAjcn7Gxsenp6bm5ue7u7r6+vo9fq8XFxYaGBphOtre3R0dHV1dXh4eHURcn/Lu0tERKJIMbDow1BEEIBMLAwABMGHAb4bD19XUgg+0+QPIP5qJ0dXWxsbHx8vLuJhbpD6ik/1r5Sjr4Kv956evri46OlpKSQgsTbm9ve3h4HDly5Mu5GV/ld8kf0YZEInF8fLyqqgrKyP3lffoqX+WrgIBdU1RUhFZHAZmfn4eCVrAJ81X+EvnKsPkqvy0EAmFmZmbHiuyr/Cdlh9Ngc3Nzfn5+YWFh9yWQvspvyldt+FV+W4hEIjjC/qc78lW+yr9R/rg2/LjeCCqkHu7dpGrj8fiPm9rY2Ojp6fncT3xS8Hj8zMwM1IL489yB/5uCw+FIk2FJndn/GUE3NNbX138Xxv0P/NC/r/HPycebP793h2qXzf4flz92V/+4NmxqahIVFf1k7jc4Fi0sLNLS0nbTVEB